Aromatic carbon from low-temperature biochar enhances bacterial phosphorus solubilization under saline-alkaline stress - Ziyi Ge; Shiyun Gan; Jiayi Li; Ziyue Xu; Siyu Wang; Xu Su; Yixuan Chen; Li Lin; Song Gao; Jun Meng (Bioresource Technology, 2027)

Experimental study and mechanism analysis of ammonia-coal co-combustion: impacts on ignition delay, combustion intensity, and char structure - Jingyan Wang; Sheng Su; Hanjian Li; Rongfei Li; Kai Xu; Jun Xu; Long Jiang; Yi Wang; Song Hu; Jun Xiang (Fuel, 2026)

Source-controlled K isotope variations in diverse granitic rocks - Wen-Jun Li; Ben-Xun Su; Zi-Yi Ding; Shan Li; Shan-Ke Liu (Lithos, 2026)

Mechanochemical destruction of per- and polyfluoroalkyl substances in solvent-free solid media: a green remediation strategy - Jun Hu; Xiaofei Yang; Xueqiang Li; Feng Yan; Guodong Su; Haixiang Cheng; Chen Chen; Jianming Yu; Zhimin Qiang (Journal of Environmental Sciences, 2026)

Multi-class urinary antibiotic exposure, dietary sources, and childhood overweight and obesity risk through lipid metabolic disruption: evidence from multicenter cohorts in China - Xinli Song; Jieyu Liu; Li Chen; Yi Zhang; Ruolin Wang; Jianuo Jiang; Lan Zhang; Yanle Xiong; Jingyang Su; Ziqi Dong; Yang Qin; Dengcheng Zhang; et al. (Environmental Pollution, 2026)

Manipulating electronic structure via entropy engineering in Mn-based Prussian blue analogue for efficient and robust capacitive deionization desalination - He Ren; Xuhui Su; Yize Li; Lintong Hu; Chunyan Li; Lei Yang; Chao Yan; Jun Yang (Desalination, 2026)

Benzimidazole functionalization enables efficient multi-resonance TADF with accelerated spin-flipping and balanced charge transport - Ji-Hua Tan; Si-Wei Chen; Xin-Lu Li; Han-Nan Shi; Xiao-Long Liu; Yao-Zu Su; Xiaofeng Wang; Jun-Hua Zhuang; Chengxiang Shi; Jia-Ming Jin; Shaoyun Yin; Jia-Xiong Chen; et al. (Chemical Engineering Journal, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

“Trojan horse” strategy-guided hydroxybutyl chitosan-based dynamic crosslinked nanofibrous membrane: A multifunctional platform for treating drug-resistant bacterial wounds - Xiao Zhou; Huacheng Tang; Yaxuan He; Yingxi Li; Shuang Liu; Ying Wang; Shengxin Su; Yun Duan; Qing Li; Fuchen Jiang; Xiaomin Lai; Qiangnu Zhang; et al. (Chemical Engineering Journal, 2026)

Low-cost pillar-ligand engineering toward ultramicroporous MOFs for efficient SF6/N2 separation - Biao Fu; Hui-Ting Zheng; Rui-Ming Li; Duo Yue; Liang Song; Zhang-Wen Wei; Robert Langer; Mihail Barboiu; Ji-Jun Jiang; Cheng-Yong Su (Chemical Engineering Journal, 2026)

Aging and photodegradation of polycyclic aromatic compounds (PACs) emitted from biomass burning under sunlight and ultraviolet radiation - Ya-Jing Li; Zhen-Shan Huang; Yu-Ping Chen; Zhi-Hui Su; Yi-Huan Chen; Yuan Zeng; Yu-Qi Huang; Yu-Feng Guan; She-Jun Chen (Atmospheric Environment, 2026)

Harmful gas generation potential and disaster mechanisms in coastal sediments of Shenzhen Bay, China: Insights from geochemical characteristics and depositional environment - Yuxuan Liu; Peidong Su; Peng Qiu; Yougui Li; Jun Sasaki (Applied Geochemistry, 2026)

Surface interception and transport of 14C-labeled polystyrene nanoplastics by benthic marine organisms - Wenwen Song; Dongxu Li; Jun Zhang; Ziyun Huang; Hongjie Zhang; Changhong Liu; Aijun Miao; Yu Su; Rong Ji (Marine Environmental Research, 2026)

Occurrence, variation and risks of viruses in aerosols during rural wastewater collection, treatment and discharge - Yingming Zhu; Su Xu; Yu Zhou; Ruiqi Quan; Jun Zhan; Xuesong Guo; Lin Li; Junxin Liu (Journal of Cleaner Production, 2026)

Linking botany and mineral exploration: Alhagi sparsifolia as a potential indicator for Ni-Cu sulfide deposits - Meng-Meng Cui; Ben-Xun Su; Shan-Ke Liu; Hui-Li Yan; Wen-Jun Li; Bing-Yu Gao; Jing Wang; Zhen-Yan He; Shu-Kuan Wu; Ye-Tao Tang (Journal of Asian Earth Sciences, 2026)

“Lotus leaf meets nacre”: a dual biomimetic approach to creating highly humidity-stable films with exceptional barrier properties for food packaging - Ningkang Deng; Jinsong Zeng; Pengfei Li; Junzhang Wu; Jianqiao Su; Zhiqiang Gong; Yuan Peng; Ting Yao; Jinpeng Li; Daxian Cao; Bin Wang; Jun Xu; et al. (Food Chemistry, 2026)

Regulation of corn starch gel's rheological properties and entanglement behavior by spring-dextrin with different degrees of polymerization - Qirong Li; Wenxiu Zhao; Songye Jun; Jiugang Yuan; Bomou Ma; Jing Su; Jin Xu (Food Hydrocolloids, 2026)

Methodology of quantifying the infiltration airflow of platform screen doors in subway stations based on pressure characteristics and air balance - Zhixuan Li; Yaoyu Zhu; Zhuoxiang Li; Moyun Liu; Yongjiu Lai; Jun Liu; Shaochen Tian; Xing Su (Energy and Buildings, 2026)

Investigation of the regulatory effects of the initial oxidation–reduction potential on lactic acid-producing bacteria in culture and silage fermentation and its metabolic mechanism - Mengxin Li; Yuanjiang Rong; Qiang Yu; Ya Su; Yulong Xi; Yixi Long; Yixiao Xie; Hong Sun; Jun Hao; Fuyu Yang; Yulong Zheng (Bioresource Technology, 2026)

Species Diversity, Parasitism Rates, Longevity, and Population Dynamics of the Parasitoid Complex Attacking Ophelimus bipolaris in China - Jin Hu; Yuan-Hao Li; Jing-Hui Su; Jin-Bo Sun; Guo-Bao Qin; Yan Qin; Lai-Feng Luo; Lin-Xia Feng; Kai-Jian Han; Zoya Yefremova; Jun Li; Xia-Lin Zheng (Neotropical Entomology, 2026)

The evaluation of biological effects of artesunate on ovarian cancer using three-dimensional cell culture methods - Yijun Yuan; Xiaojing Luo; Longyu Tang; Tianwen He; Xinru Zou; Lu Feng; Bin Su; Jia Wu; Jun Li; Dongqin Xiao (Cell and Tissue Banking, 2026)
Ovarian cancer (OC) is one of the most aggressive malignancies, with high mortality rates largely attributed to late-stage diagnosis, tumor heterogeneity, recurrence, and resistance to chemotherapy. Artesunate (ART), a water-soluble derivative traditionally used to treat malaria, has recently gained attention as a promising anticancer agent. Recently, studies have shown that ART can inhibit the migration and invasion of cancer cells. However, theses studies are always based on conventional two-dimensional (2D) culture models, which neglect the complex interactions between cells and the extracellular matrix (ECM) or in vivo microenvironment. To address these challenges, in this study, honeycomb-like gelatin methacryloyl (GelMA) hydrogel microspheres as a three-dimensional (3D) culture platform were introduced to mimic the native ECM microenvironment and assess the effects of ART on ovarian cancer cells. The results showed that these GelMA microspheres exhibited a uniform and highly porous structure, which supported cell adhesion, proliferation, and migration. Notably, 3D culture promoted DNA synthesis and induced G1-to-S phase transition, indicating enhanced proliferative capacity. Furthermore, ovarian cancer cells cultured in 3D exhibited stronger invasive and chemoresistant phenotypes. RNA sequencing revealed that after ART treatment, tumor-related proliferation and invasion genes of ovarian cancer cells were significantly up-regulated under 3D culture compared with 2D culture. This might be related to the up-regulation of TNF signaling pathway, NF-kappa B signaling pathway, and Pl3K-Akt signaling pathway. Correspondly, epithelial-mesenchymal transition (EMT) of ovarian cancer cells was markedly enhanced when cultured on GelMA hydrogel microspheres after ART treatment. These effects might be attributed to the altered microenvironment provided by the GelMA hydrogel microspheres, which could be responsible for the enhanced resistance of ovarian cancer cells to ART. These findings suggest that, compared to traditional 2D. These findings suggest that, compared to traditional 2D culture, the 3D extracellular matrix-based system better mimics the in vivo tumor architecture, thereby improving the sensitivity of anticancer drug screening and offering a more reliable platform for evaluating drug resistance and tumor cell heterogeneity.

Centrifuge tests of the uplift behavior of an immersed tunnel on liquefiable sand deposit under horizontal and bidirectional excitations - Huanzhu Zhou; Shengan Liu; Bin Li; Weiyun Chen; Lei Su; Jun-jie Zheng; Yewei Zheng (Tunnelling and Underground Space Technology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Zn2 +-doped and -NH2-modified TiO2-SiO2 composite for highly efficient and selective removal of Sr2+ from nuclear wastewater - Jun Liao; Ke Su; Heyu Luo; Pan Li; Nishan Zhong; Zijia Zhang; Ling Ding (Process Safety and Environmental Protection, 2026)

Corrigendum to “Tracing material transport during subduction inception: Insights from potassium isotopes in the crustal sequence of the Troodos ophiolite” [Geochim. Cosmochim. Acta 373 (2024) 259–270] - Qi-Qi Pan; Yan Xiao; Ben-Xun Su; Paul T. Robinson; Wen-Jun Li; Jing Wang; Xia Liu (Geochimica et Cosmochimica Acta, 2026)

Structural characterization, functional properties and formation mechanism of alkali-thermal induced egg white gel: from macroscopic gel properties to molecular conformation and interactions - Shende Hu; Xiaochen Liu; Luping Gu; Cuihua Chang; Junhua Li; Xiaosan Wang; Jun Sun; Shijian Dong; Han Jiao; Yanjun Yang; Yujie Su (Food Research International, 2026)

Dual-lignin molecular regulation enables intrinsic photothermal polyurethane elastomers with simultaneously high stiffness and toughness - Xiuru Su; Chuan Xu; Mengya Sun; Jun Li (Chemical Engineering Journal, 2026)

Deletion of electron-bifurcating [FeFe]-hydrogenase enhances H2-driven CO2 fixation and ethanol production in Clostridium ljungdahlii - Zhi-Qiong Wen; Yu-Zhen Li; Hai-Jia Su; Jun-Zhe Zhang; Zi-Yong Liu; Shu-Ning Wang; Hui Wang; Fu-Li Li; Xiao-Qing Ma (Bioresource Technology, 2026)

Two newly isolated compounds from Hansenia weberbaueriana and their anti-inflammatory potential - Jie Li; Su Hu; Li Huang; Li-Lian Zhao; Li-Jun Huang; Wei-Jun Dong; Wei-Zhen Dong; Yun Deng; Da-Le Guo (Natural Product Research, 2026)

Solar light irradiation activated dichloramine for efficient abatement of micropollutants - Peng Su; Wenjun Zhang; Haochen Zhang; Haonan Lu; Qiuling Lu; Kai Wang; Yuying Li; Xiaolong Xu; Changyu Liu; Jun Ma; Tao Yang (Water Research, 2026)

Investigation on the Crack Propagation of Edge-Fissured Slope-Shaped Specimens: Coupling Effects of Bedding Planes and Edge Fissures - Hesi Xu; Jun Yu; Yifei Li; Xianzheng Zhu; Zhengyang Su; Shuyang Yu (Transportation Geotechnics, 2026)

Monomeric and dimeric sesquiterpenoids from Artemisia princeps Pamp and their anti-inflammatory activity - Hong-Xia Li; Si-Yu Bai; Bao-Jun Su; Dong Liang; Ning Li; Gui-Jie Zhang (Phytochemistry, 2026)

Zwitterionic engineering of chitosan enables highly soluble, antibacterial films for sustainable fruit preservation - Dahai Liu; Xiaoxiao Wang; Jing Xu; Fang Yang; Riwang Li; Qiang Fu; Jie Li; Jieyan Wang; Xiu Wang; Haotian Lan; Ziyin Liu; Yafei Su; et al. (Food Research International, 2026)

Radiofrequency-responsive nanogel co-delivering cisplatin and EGCG for enhancing the efficacy of hepatocellular carcinoma interventional therapy by thermoresistance modulation and immune remodeling - Yaowei Bai; Mengqin Guo; Kexin Wang; Yu Lei; Jun Wu; Bo Sun; Wenlong Wu; Xiatong Bai; Yang Su; Ling Li; Yanbing Zhao; Chuansheng Zheng; et al. (Chemical Engineering Journal, 2026)

Shifts in sources of non-methane hydrocarbons in the most ozone-polluted region of the Pearl River Delta, China (2020–2023) - Li Luan; Zhen Zhou; Shenlang Zhang; Jun Tao; Xihua Li; Shuzhen Su; Zhisheng Zhang; Guanghui Li; Bin Jiang; Daocheng Gong; Zhanyi Zhang; Boguang Wang (Atmospheric Pollution Research, 2026)

Artemisinin derivative SM934 targets α-enolase to inhibit PEP-mediated TAK1 stabilization and inflammation - Jun Pan; Yuwei Zhang; Zhiwei Du; Yuanyuan Huang; Yu Wang; Miya Su; Yuting Cai; Weiya Xu; Lili Chen; Chengdong Huang; Di Cui; Dongsheng Chen; et al. (Science China Life Sciences, 2026)

First report of scale drop disease virus (SDDV) infection in cultured silver pomfret (Pampus argenteus) in China: Isolation and pathogenic characterization - Su-Ming Zhou; Yang-Yang Bai; Deng-Feng Li; Jia-Song Xie; Ya-Jun Wang; Fei Yin (Aquaculture, 2026)

Sustainable hard carbon anodes derived from Paulownia wood for high-performance sodium-ion batteries - Ansheng Wei; Yuchao Su; Fude Li; Jun Li; Liqiang Zhang (Journal of Environmental Chemical Engineering, 2026)

Evolution and role of manganese-transforming bacterial microorganisms during natural manganese-tailing succession - Chuan Wu; Yahui Wu; Jiahao Pan; Yangtao Lv; Waichin Li; Min Hu; Jun Wang; Shiming Su; Qi Zou; Shengguo Xue (Journal of Environmental Sciences, 2026)

Magnesium isotope geochemistry in continental flood basalts: implications for mantle source heterogeneity - Sakine Moradi; Lie-Meng Chen; Peter C. Lightfoot; Kang-Jun Huang; Qiao Su; Song-Yue Yu; Li-Juan Zhu; Rui-Zhong Hu (Geochimica et Cosmochimica Acta, 2026)

Understanding the differences in ignition and combustion characteristics between raw coal and pyrolyzed char: A combined PLIF measurement and DFT calculation - Yawei Song; Sheng Su; Qifu Lin; Longwei Chen; Chengzhou Liu; Weiye Chen; Zhenyang Li; Yiman Jiang; Dianwu Wu; Hansheng Feng; Guangnan Luo; Jun Xiang (Fuel, 2026)

Predictive Multi-Physics coupling coal combustion model under rapid heating - Hanjian Li; Ying Zhao; Shichen Ding; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Huanying Chi (Fuel, 2026)

Interventional mechanisms of antioxidants on flavor profile modification in the fermented egg white powder system - Ru-yi Zhang; Zhi-shuo Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2026)

Integrating filtration, pollutant adsorption, and thermal management for enhanced respiratory health: A synergistic framework for next-generation protective masks - Yating Tang; Yun Su; Yiwei Wu; Zhuoling Yu; Mengxian Xu; Miao Tian; Jun Li (Building and Environment, 2026)

Chronic fluoride exposure induces tissue damage, oxidative stress, and immune dysfunction in juvenile crucian carp (Carassius auratus) - Jingjing Zhang; Xuejun Gao; Jun Ma; Limin Wu; Xi Shi; Qing Su; Xuejun Li; Yongjing Li (Fish Physiology and Biochemistry, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Genomic insights into adaptation and microevolution of two novel non-AOA Nitrososphaeria, Acidarchaeum fankouense and Thermosulfuris yongpingense, in acid mine drainage ecosystems - Licao Chang; Xikai Su; Wenzhe Hu; Yun Fang; Jun Liu; Jintian Li; Linan Huang; Wensheng Shu (Systematic and Applied Microbiology, 2026)

Establishment of a coupled anammox-sulfur driven autotrophic denitrification system for nitrogen removal from nitrogen-rich wastewater - Wei Xu; Jun Li; Qian Yang; Junwei Wu; Liang Xu; Xiaomei Su; Feng Dong; Xiao Xiao; Faqian Sun (Process Safety and Environmental Protection, 2026)

Li and K isotope fractionation controlled by minerals during magmatic differentiation of Changbaishan, NE China - Li-Zhi Yan; Ben-Xun Su; Wen-Jun Li; Shan-Ke Liu; Yan Xiao; Patrick Asamoah Sakyi (Lithos, 2026)

Transgenerational effects of short-term low-temperature stress on development, fecundity, and cold tolerance of Megabruchidius dorsalis - Min Li; Yonglan Pan; Jingjing Shi; Jun Liao; Yuting Yan; Silin Chen; Fei Su; Runa Zhao; Yue Wang; Lei Gao; Guy Smagghe; Chengxu Wu; et al. (Journal of Stored Products Research, 2026)

Coupling bayesian optimization and multi-paradigm ensemble learning to predict lead remediation in microbially induced carbonate precipitation: From model performance to crystalline control windows - Yan Wang; Chunli Zheng; Ruijing Su; Li Fan; Mingdong Chang; Nuo Liu; Fangzhou Li; Jun Wu (Journal of Hazardous Materials, 2026)

Preparation and characterization of chitosan‑sodium alginate complex edible casings incorporated with tea polyphenols and their application in dry-cured sausages - Huanhuan Li; Yanting Gao; Teng Xu; Ke Zhao; Mingwei Su; Jun He; Honggang Tang (Food Chemistry, 2026)

Polycyclic aromatic hydrocarbon exposure and mitochondrial DNA copy number: Opposing roles of oxidative stress and inflammation - Si Zhou; Wenzhe Su; Lingli Zeng; Jia He; Jun Yuan; Rongfei Peng; Juntao Li; Lei Tan (Environmental Pollution, 2026)

Structural evolution-based ancestral sequence reconstruction of medium-chain alcohol dehydrogenase for efficient synthesis of fused-ring chiral alcohols - Jun Wang; Songyin Zhao; Lehang Li; Manman Zhu; Man Zou; Xin Su; Jie Gu; Yan Xu; Yao Nie (Bioresource Technology, 2026)

Spatiotemporal characteristics and meteorological drivers of background ozone in China's Pearl River Delta region - Xiaoyong Liu; Jun Yan; Fangcheng Su; Hongrui Li; Wei Wei; Hui Gao; Junhui Yan (Atmospheric Pollution Research, 2026)

New sesquiterpenoids from the flowers of Pentanema britannicum with cytotoxicity activities - Jun-Hui Zhang; Ping He; Sheng-He Yang; Jia-Li Lang; Yan Fu; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Immunogenicity and safety of an Escherichia coli-produced 9-valent HPV vaccine in adolescents aged 9 to 17 compared with young women - Yulin Jing; Xiaowen Hu; Li Zhang; Jiangyahui Wang; Fei Yang; Rong Wang; Ying Jiang; Lingling Nie; Zhongqiang Jin; Xuecheng Liu; Sihai Li; Chao Du; et al. (Science Bulletin, 2026)

Thermal degradation kinetics and behavior of MPN from Ginkgo biloba - Yu Kong; Yi-yuan Zhou; Ya-ping Wang; Xiao-fang Wang; Shan Duan; Mo-wen Su; Juan Zhao; Li-min Wang; Qing Kang; Xin-jun Du (Journal of Food Engineering, 2026)

Mechanistic insights into the enhanced degradation of hydroxychloroquine by singlet oxygen in PMS and PMS/Cl2 systems: A comparative study - Zi-Han Feng; Zhen-Zhen Li; Dong-Su Bi; Fu-Xiang Tian; Ling-Yao Meng; Yan-Ting Jia; Yu-Qiong Gao; Xiao-Jun Hu (Journal of Environmental Management, 2026)

Density-dependent functional thresholds and early-warning indicators of alpine meadow degradation under plateau pika (Ochotona curzoniae) and zokor (Myospalax baileyi) disturbance: A meta-analysis - Huan Li; Xiaomei Sun; Qin Zhang; Li Wang; Kehong Xu; Fujiao Wang; Zhengwei Ren; Honglin Li; Junhu Su; Jun Zhang (Journal of Environmental Management, 2026)

Polystyrene microplastics impaired decidualization in mice via oxidative stress and inflammation and disrupted the reproductive function of their female offspring - Weike Li; Boyin Tan; Jun Xiong; Jiani Diao; Jing Wang; Jing Long; Zhenyin Chen; Yuguang He; Xuemei Chen; Fei Han; Fangfang Li; Junlin He; et al. (Journal of Environmental Sciences, 2026)

Multi-omics reveals the mechanism of delayed lipid oxidation and proteolysis in fish fillets preserved by high-voltage electrostatic field and grape pomace-chitosan coating - Bingqiang Xie; Xia Li; Wenbo Kang; Jiantao Wang; Jing Su; Jun Wang (Food Chemistry, 2026)

Quantifying fault-controlled radon degassing induced by Pacific Plate subduction in the Miaodao Archipelago, North China - Shujuan Su; Ying Li; Chang Lu; Yanming Yang; Zhaofei Liu; Fengxia Sun; Jun Liu; Qinglin Wang; Zhigang Liu; Hao Sun; Yaowen Zhang; Chunhong Zou; et al. (International Journal of Earth Sciences, 2026)

Body size drives male reproductive success through nest competition and paternal care in the toad Leptobrachium boringii - Raziya Abliz; Wei Zhang; Shuang Liu; Rufeng Xiong; Chunhua Huang; Jun Li; Mian Zhao; Zhirong Gu; Man Su; Wei Liu; Hua Wu (Animal Behaviour, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

Molecular insights into the antifungal activity of Bacillus velezensis JLU-53 against Cochliobolus heterostrophus in maize - Maoxiang Li; Mengjiao Jia; Yuanyuan Tian; Longhao Su; Hongran Tian; Guining Liu; Jun Hu; Xianghui Zhang (Pesticide Biochemistry and Physiology, 2026)

Effect of CO2 and H2O on pyrolysis characteristics and structural evolution of Zhundong coal under rapid heating rate - Huanying Chi; Shichen Ding; Ying Zhao; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Hanjian Li (Fuel, 2026)

Effect of CaO on the reaction between NH3 and NO under high-temperature reducing atmosphere in cement kilns: An experimental and simulation study - Mengchuan Jia; Sheng Su; Wei Deng; Hanjian Li; Kai Xu; Long Jiang; Jun Xu; Yi Wang; Song Hu; Jun Xiang (Fuel, 2026)

Genome-wide characterization of soybean alcohol dehydrogenase (ADH) genes identifies GmADH13 as a positive regulator of the salt stress response - Sihui Wang; Zhiyuan Xu; Peng Cheng; Jun Yang; Qiang Hao; Jinfang Wang; Ziqian Cheng; Lingshi Xia; Zhenbang Hu; Xin Li; Anyu Su (Theoretical and Applied Genetics, 2026)

KNN-Transformer Hybrid Model for High-Precision Lithofacies Identification in Heterogeneous Reservoirs - Jun-lei Su; Xu Dong; Pei-xuan Li; Xue-ying Shi; Yu Zeng; Jia-wei Tang; Ren-jie Yang (Applied Geophysics, 2026)

UVB-activated permanganate enables rapid emerging organic contaminants decontamination through synergistic HO• and reactive manganese species - Ping Li; Peng Su; Qixiao Lv; Qiuling Lu; Ying Xu; Xiangyang Hou; Jucai Xu; Jun Ma; Tao Yang (Water Research, 2026)

Rapid prediction of cellulose, hemicellulose, and lignin content in biomass using FTIR based on transfer learning - Junmeng Li; Dezhi Chen; Zhou Fang; Xing Hu; Xiaochuan Chen; Jun Xu; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Journal of Cleaner Production, 2026)

Imidazolyl ionic liquid-based hypercrosslinked polymers as adsorbents for reversible capture of iodine - Xiaomeng Su; Ming Zhao; Liqiu Sun; Yue Yu; Jianjun Wang; Liyan Wang; Jun Li; Dan Wang; Liying Qi; Kuo Zhang; Zhichun Shi (Journal of Environmental Chemical Engineering, 2026)

Effects of volatile–char interaction on the chemical structure during coal pyrolysis: An in-situ EPR study - Haotian Xu; Guangying Li; Wei Deng; Kai Xu; Jun Xu; Long Jiang; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Fuel, 2026)

Investigation on in-situ and ex-situ catalysis of metal salt in biomass photo-thermal pyrolysis: Effects on decoupled primary and secondary reactions - Dexin Huang; Gongxiang Song; Ruochen Li; Kai Xu; Jun Xu; Long Jiang; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Fuel, 2026)

Lactic acid modulates empty-cup aroma persistence in Baijiu via molecular interaction mechanisms: a case study of strong-aroma and soy-sauce-aroma Baijiu - Qing-Ru Liu; Shun-Hua Zhang; Xiao-Juan Zhang; Zheng-Juan Zhu; Ru-Yi Li; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Guan-Yu Fang; Qing-Qing Liu; Yong-Jun Yuan; et al. (Food Chemistry, 2026)

The DTH8-SD1 pair regulates panicle architecture in rice - Su Su; Jun Hong; Ling Li; Xiaofei Chen; Cai Chen; Jianxin Shi (Theoretical and Applied Genetics, 2026)

Ingestion of nanoplastic-contaminated feed induces oxidative stress and impairs muscle quality in hybrid yellow catfish (Pelteobagrus fulvidraco × Pelteobagrus vachellii) - Zeliang Su; Huandi Guo; Yang Long; Kai Chen; Fang Chen; Linyong Zhi; Xiaoping Huang; Zhen Li; Liangfu Wei; Guanglong Chen; Jun Wang (Aquaculture, 2026)

Analysis of fatty acid β-oxidation-related family genes in bivalves and their roles in noble scallop Chlamys nobilis under low-temperature stress - Hailong Su; Yifan Li; Yaoting Liu; Beiyu Yan; Naiqian Zhao; Shitong Liu; Haixin Hu; Jun Xu; Tao Zhang; Feng He; Hongkuan Zhang; Huaiping Zheng (Aquaculture, 2026)

Groundwater volume loss and land subsidence in the North China plain investigated using wide-area InSAR surveying and mechanical modeling - Xing Zhang; Jun Hu; Mahdi Motagh; Mingjia Li; Yuedong Wang; Qiuhong Yang; Guangli Su; Haigang Wang (Remote Sensing of Environment, 2026)

Assessment on intestinal health from polylactic acid microplastics degradation on rare minnow (Gobiocypris rarus): Inflammation regulation by mitochondrial dysfunction - Liangxia Su; Xue Xia; Miaomiao Hou; Yifan Ding; Huanhuan Li; Jianwei Wang; Yongfeng He; Jun Liu (Environmental Research, 2026)

The low R = d/d high-entropy strategy enables high-performance sodium layered oxide cathode materials - Jun-Jie Liao; Min Wen; Wei-Wei Yuan; Qi-Lin Zheng; Kang Chen; Fu-Sheng Zhou; Zhen-Xin Qiu; Su-Yun Wang; Li-Li Wang; Lituo Zheng; Yiyin Huang; Jia-Xin Li; et al. (Chemical Engineering Journal, 2026)

Long Non-Coding RNA PVT1 Inhibits Apoptosis Through the miR-30d-5p/CaMKIIδ Axis in Hypoxic–Ischemic Brain Injury - Fengyan Zhao; Junyan Liu; Zihong Xiong; Lingyi Huang; Yuanyuan Zhao; Shiping Li; Junjie Ying; Qian Liu; Shaopu Wang; Xiaojuan Su; Jun Tang; Yi Qu; et al. (Molecular Neurobiology, 2026)

Optimisation of wheatgrass extraction using composite weighting-response surface methodology with phytochemical profiling and network pharmacology-based target prediction - Yanru Wang; Weiping Li; Meijuan Hou; Jun Su; Li Wu; Qirui Dai; Zeyu Wang; Danhong Wu (Natural Product Research, 2025)

Performance of a simultaneous nitrification, denitrification, anaerobic ammonium oxidation, and phosphorus removal (AOA-SNDAPR) system dominated by Candidatus_Competibacter and Defluviicoccus for advanced nutrient removal - Wenqiang Wang; Qu Wang; Li Wang; Yang Su; Licheng Zhang; Jun Li; Dong Li (Journal of Environmental Chemical Engineering, 2025)

Mechanism study on the effect of ammonium bisulfate on the adhesion characteristics of fly ash - Mengxia Qing; Yunda Su; Jieyu Chen; Xinao Li; Lele Wang; Zhe Zhu; Liang Liu; Jun Xiang (Fuel, 2025)

Interactive effect of various fatty acids and the Maillard reaction of sesame meal enzymatic hydrolysates on aroma generation - Qing-qing Ruan; Bei-bei Hu; Kai-yue Su; Jun-ru Li; Wen-ting Yin; Zi-qi Han; Yu-xin Liu; Xiao-shuang Cai (Food Research International, 2025)

Effects of inducing conditions on emulsion gel properties of peanut protein isolation-cellulose nanofiber: As extrusion-based 3D food printing inks - Rui Wang; Chun-yan Su; Dong Li; Li-jun Wang (Food Chemistry, 2025)

Electrostatic spray drying enhances transferrin hydrophilicity for improved rosmarinic acid binding: Insights into biological activity and molecular mechanism - Ru-yi Zhang; Zhi-shuo Zhang; Ting-ting Tang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Yan-jun Yang; Cui-hua Chang (Food Chemistry, 2025)

Integrative transcriptomics and QTL analysis identify lactoperoxidase and deubiquitinase as key targets for mastitis control in dairy animals - Jie Su; Fei Wang; Runshi Li; Lin Guo; Xianghai Ma; Xiaoyan Wang; Junyu Zhang; Shuaitao Lian; Jiaoxiong Xue; Jianglin Zhao; Yong Zhang; Xu Liu; et al. (Food Bioscience, 2025)

How hydrophobic deep eutectic solvents as liquid-liquid extractants remove Pb2+ from wastewater: Material properties, extraction behavior, and molecular-level mechanism simulation? - Jie Qian; Ying-hua Li; Di Luo; Fei Su; Si-nan Liu; Jun-xiang Wang; Wan-qi Li (Environmental Research, 2025)

Homogeneous MgF2-engineered Na surface architecture enabling uniform ion deposition in ultra-stable sodium metal batteries - Xueming Su; Junjie Fu; Lin Luo; Xiaoquan Yang; Yue Li; Weijiang Hu; Qing Li; Qingye Li; Chencheng Sun; Jun Yang; Hongwei Gu (Chemical Engineering Journal, 2025)

Hydrogel engineering for cardiac patches and cardiovascular organ-on-a-chip - Qingtong Liu; Haiyan Zhang; Xiatong Pan; Jun Chen; Weiguang Su; Anqing Li; Guohua Liu; Li Wang (Chemical Engineering Journal, 2025)

Valorization of blueberry pomace and red mud to zero valent iron biochar for antibiotic degradation with diminishment of toxic reagents - Xu Su; Jie Han; Yuwei Huang; Xuanming Wang; Siyu Wang; Ziyi Ge; Hechong Yuan; Juying Liu; Xuerong Xiang; Fan Xia; Li Lin; Yu Lan; et al. (Bioresource Technology, 2025)

CRIF counteracts oncogenic Ras and regulates heterochromatin - Su Jun Lim; Jinghong Li; Willis X. Li (Molecular Genetics and Genomics, 2025)

Serum cortisol and AdipoR2 rs12342 were involved in the correlation between stress and serum cholesterol in a gender-specific manner - Yi Lin Shen; Qi Wei Guo; Xue Cheng Li; Ke Xin Jia; Jun Yi Liu; Yan Zhi Yi; Jun Tao Ren; Jia Jing Cai; Guo Ming Su; Jia Lin; Ding Zhi Fang (Metabolic Brain Disease, 2025)

BmeIF4E2 promotes AcMNPV infection in the silkworm, Bombyx mori, by direct interaction - Xin-Yi Ding; Jiang-Zhi Su; Wen-Jing Yu; Qian-Qian Jiao; Zuo-Min Shao; Ai-Jun Wan; Sheng Qin; Xia Sun; Xue-Yang Wang; Ding-Ding Lü; Mu-Wang Li (Pesticide Biochemistry and Physiology, 2025)

Microplastic aging and plastisphere succession in mangrove sediments: Mechanisms, microbial interactions, and degradation potential - Yuanyuan Su; Jun Lei; Xiaoping Diao; Licheng Peng; Lianzheng Yin; Yongqiang Qin; Wen Zhang; Ping Li (Journal of Hazardous Materials, 2025)

Cumulative effect of PM2.5 chemical components surpasses PM2.5 mass on hypertension in older adults: A China-based national analysis - Chen Chen; Binbin Su; Yunhe Wang; Yihao Zhao; Yutong Wu; Jun Li; Yanan Luo; Xiaoying Zheng (Journal of Environmental Sciences, 2025)

Unraveling Qu-aroma variation between inner and outer layers of medium-temperature Daqu: A multi-omics and sensory approach - Sheng-Bing Yang; Zhen-Ming Lu; Han-Jun Shen; Jun-Jie Fu; Yang Yang; Xiao-Juan Zhang; Li-Juan Chai; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Feasibility assessment of online coal quality monitoring based on concentrating photothermal rapid combustion: Insights from neural network and explainability analysis - Ying Wu; Pengfeng Yu; Jun Xu; Hanjian Li; Kai Xu; Huanying Chi; Long Jiang; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Fuel, 2025)

Insight into the cryoprotective mechanisms of lysine combined with sorbitol on silver carp surimi during frozen storage: Gel properties, molecular conformation and interactions - Lingxia Su; Jingrou Zhao; Chen Wang; Huiling Li; Wenjun Liu; Xumei Wang; Jun Liu; Zongcai Tu; Yanhong Shao (Food Research International, 2025)

Extending the functionalities of the Biome-BGC model to simulate carbon storage in unmanaged and managed mixed forests - Ke Yan; Menglin Su; Haikui Li; Tongli Wang; Jun Lu; Xiangfu Wang; Weifeng Wang (Computers and Electronics in Agriculture, 2025)

Furofuran and tetrahydrofuran lignans from Lancea tibetica - Wenbo Li; Fuhua Zhu; Lu Tang; Jun Xu; Xiaoying Zhang; Zhicheng Duan; Wei Zhang; Ping Hai; Yongbiao Zheng; Haiqing Liu; Xia Li; Yanfang Su (Phytochemistry, 2025)

Synergistic highly sensitive electrochemical detection of enrofloxacin using Eichhornia crassipes-derived carbon dots and molecularly imprinted polymer networks - Chang-Hong Wang; Yi-Yue Tang; Yan-Jun Li; Fu-Lan Xiao; Lian-Di Zhou; Qi-Hui Zhang; Chun-Su Yuan (Journal of Environmental Chemical Engineering, 2025)

Hierarchically shortened b-axis ZSM-5 nanosheet endows super catalytic stability for methanol-to-hydrocarbons reaction - Zhan Liu; Ying-Jun He; Zhi-Yi Hu; Jia-Min Lyu; Shen Yu; Yu-Hang Song; Xiao-Qiang Liao; Zhi-Wen Yin; Ming-Hui Sun; Yu-Chun Zhi; Li-Hua Chen; Bao-Lian Su (Chemical Engineering Journal, 2025)

Smart window with high solar blocking capability: Integrating electrochromic TiO2-viologen composite film and thermochromic electrolyte - Fangyuan Sun; Haibo Wu; Miao Li; Yiqi Xu; Yuanxin Yan; Yonghao Chen; Yanan He; Shiqi Zu; Xueqing Xu; Hsien-Yi Hsu; Fengyu Su; Yanqing Tian; et al. (Chemical Engineering Journal, 2025)

Mechanically robust lignin-cellulose films with triple barrier functions for antagonistic food preservation - Ningkang Deng; Yue Ma; Pengfei Li; Jinsong Zeng; Zhiqiang Gong; Jianqiao Su; Jinpeng Li; Daxian Cao; Bin Wang; Jun Xu; Kefu Chen (Chemical Engineering Journal, 2025)

Nature's answer to flexible electronics: Polysaccharide-based hydrogel sensors - Xinyue Liu; Chun-yan Su; Lu-yao Zheng; Dong Li; Li-jun Wang (Carbohydrate Polymers, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Efficient permanganate activation under UV 222 nm irradiation for enhanced pollutant abatement - Haochen Zhang; Peng Su; Maoju Jiang; Chenlong Liu; Qixiao Lv; Wenqi Li; Xiangyang Hou; Junhui Zhou; Shuo Li; Bin Zhang; Bei Zhang; Jun Ma; et al. (Water Research, 2025)

Paleoproterozoic crustal-derived carbonatites in Trans-North China Orogen - Shi-Ying Wang; Ben-Xun Su; Jing Wang; Shan-Ke Liu; Wen-Jun Li (Precambrian Research, 2025)

Impact of metal acetate on pyrolysis process of waste wind turbine blade to generate p-isoproprenylphenol-rich substances - Zhaoyu Chen; Qiangqiang Ren; Nan Li; Jialin Zhang; Zihui Xiong; Song Hu; Yi Wang; Sheng Su; Long Jiang; Jun Xu; Jun Xiang (Journal of Cleaner Production, 2025)

Interaction between persistent free radicals (PFRs) and oxygen in biochar and its impact on gasification/combustion reactivity: An in-situ EPR study - Haotian Xu; Liqun Ma; Guangying Li; Dezhi Chen; Wei Deng; Kai Xu; Jun Xu; Long Jiang; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Fuel, 2025)

Converting pig manure into biochar mitigates the antibiotic resistance of vegetable endophytes - Xue Zhou; Jun Ma; Min Qiao; Yin Wang; Zhi-Hong Cao; Jian-Qiang Su; Wan-Ying Xie; Patrick O'Connor; Gang Li (Environmental Pollution, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

Interface enhanced catalytic hydrodeoxygenation of vanillin as a bio-oil model using Ni-based catalysts - Kuan Du; Hong Li; Long Jiang; Kai Xu; Jun Xu; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Chemical Engineering Journal, 2025)

Construction of protective layer on PET fabric by utilizing hydrophilic-hydrophobic interactions for sensing, flame retardancy and thermal management properties - Weiwen Gu; Jian Liu; Xiaowei Su; Peng Qi; Xinyu Cui; Yujia Wang; Hongfei Li; Xiaoyu Gu; Jinping Xiong; Jun Sun; Sheng Zhang (Chemical Engineering Journal, 2025)

Grotthuss mechanism-enabled superfast, ultrastable, high-volumetric and ultralow temperature (−80 °C) proton storage in bulk α-MoO3 - Weifeng Liu; Zhi Zhang; Zhongxi Li; Yifan Zheng; Huanyi Liao; Yanan Zhang; Jun Su; Yihua Gao (Chemical Engineering Journal, 2025)

Chronic Anatabine Administration Attenuates Cardiovascular Activity by Targeting NF-κB/NLRP3/Caspase-1-Dependent Pyroptosis and Oxidative Stress in Paraventricular Nucleus of Hypertensive Rat - Qing Su; Shao-Jun Li; Jun-Yu Zhou; Jin-Bao Yang; Fang Zhao; Guo-Quan Zou; Jia-Xuan Ma; Qi Liu; Yuan-Yuan Feng; Cui-Ling Yang; Ying Li; Hong-Bao Li; et al. (Cardiovascular Toxicology, 2025)

Initial litter quality modulates the positive effects of soil fauna on litter mass and component loss: a global synthesis - Guiqing Zhu; Fuzhong Wu; Cuihuan Li; Kai Yue; Jun Su; Chaoxiang Yuan; Hongrong Guo; Jielu Wu; Xue Zhang; Yan Peng (Applied Soil Ecology, 2025)

Characteristics analysis of the typical vehicle-mounted megawatt-scale heat pipe cooled reactor power system - Henglong Lin; Zeguang Li; Kan Wang; Weilin Zhuge; Ganglin Yu; Hongsheng Jiang; Jingkang Li; Jun Yang; Zilin Su; Huifu Wang (Annals of Nuclear Energy, 2025)

Coupled experimental evaluation and machine learning prediction of mechanical properties of cyanide tailings cured by non-uretolytic microbially induced carbonate precipitation - Yan Wang; Yaoting Duan; Kaineng Lei; Chunli Zheng; Ruijing Su; Li Fan; Nuo Liu; Jun Wu (Process Safety and Environmental Protection, 2025)

High-precision age constraint for the Xiyingzi Bed of the Jiufotang Formation in western Liaoning, Northeast China - Li-Jun Zhang; Si-Yu Song; Shu-An Ji; Su-Chin Chang; Jahandar Ramezani; Fei Gao; Bo Wang; Hai-Chun Zhang; Da-Ran Zheng (Palaeoworld, 2025)

Viral insights into the acidification of sulfidic mine tailings - Xikai Su; Jun Liu; Licao Chang; Wenzhe Hu; Yun Fang; Jintian Li; Linan Huang; Wensheng Shu; Hailiang Dong (Journal of Hazardous Materials, 2025)

Machine learning based prediction by PlantCdMiner and experimental validation of cadmium-responsive genes in plants - Chaoqun Xu; Ling Sun; Lu-Dan Zhang; Ze-Jun Guo; Ji-Cheng Wang; Li-Han Zhuang; Dong-Na Ma; Ling-Yu Song; Jing Li; Qian-Su Ding; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2025)

Basicity regulated MgO aerogel with high adsorption capacity for medium-temperature CO2 capture - Liping Du; Aishu Li; Song Hu; Sheng Su; Yi Wang; Long Jiang; Jun Xu; Kai Xu; Jun Xiang (Journal of Cleaner Production, 2025)

Differential effects of biochar and straw incorporation on soil organic carbon: A case study on paddy cultivation in Northeast China - Hechong Yuan; Yaman Wu; Yuanyuan Sun; Juying Liu; Li Lin; Fan Xia; Xu Su; Qiang Sun; Jun Meng (Journal of Environmental Management, 2025)

Effects of isothermal and non-isothermal pyrolysis with char-loaded iron catalysts on tar removing and hydrogen yield during steam reforming of pine wood - Wei Deng; Junmeng Li; Lu Zeng; Xuepeng Wang; Xin Guo; Kai Xu; Sheng Su; Song Hu; Yi Wang; Jun Xiang (Journal of Environmental Chemical Engineering, 2025)

Advancing thermal-moisture comfort and environmental adaptability of running apparel in winter - Yuexi Zhu; Yun Su; Xin Ge; Miao Tian; Jianlin Liu; Jun Li (Energy and Buildings, 2025)

Sodium citrate enhances anaerobic fermentation of granular sludge: the multifaceted roles of structure disruption and metabolic regulation - Jinte Zou; Zhou Ye; Haibo Ma; Lei Cai; Jiaqi Yang; Fengfan Yu; Yinglong Su; Yifeng Chen; Jun Li (Water Research, 2025)

Continental melting and growth through subduction processes: Evidence from the petrogenesis of Paleozoic granitoids and gabbros in the Qinling Orogen - Zhi-Wei Fan; Bin Li; Yong-Jun Shao; Matthew J. Brzozowski; John A. Mavrogenes; Yi-Qu Xiong; Ji-Heng Su; Qing-Quan Liu (Lithos, 2025)

Correction for calcium interference in the 40Ar/39Ar dating method - Wan-Feng Zhang; Jun-Jie Wang; De-Wen Zheng; Ming Xiao; Jia Zhang; Jun-Jie Li; Yu-Lian Zhang; Ying-De Jiang; Fei Su; Li Li; Yi-Gang Xu (Icarus, 2025)

Explore the synergistic effects of Lactobacillus plantarum fermentation and tea polyphenols on the deodorization of egg white powder from the perspective of protein site competition - Ru-yi Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2025)

Characteristics of microbial carbon pump in the sediment of kelp aquaculture zone and its contribution to recalcitrant dissolved organic carbon turnover: insights into metabolic patterns and ecological functions - Jun-Yang Ma; Ji-Hua Liu; Cheng-Zhuang Chen; Yi-Ze Zhang; Zhan-Sheng Guo; Min-Peng Song; Feng Jiang; Zi-Tong Chai; Zhu Li; Su-Xian Lv; Yu-Jiao Zhen; Lu Wang; et al. (Environmental Research, 2025)

Bromine radicals and hydroxyl radicals efficiently degrade emerging organic contaminants in the UVA photolysis of bromine process - Tao Yang; Xiujuan Kong; Ge Zeng; Maoju Jiang; Linqian An; Peng Su; Qixiao Lv; Jun Ma; Juan Li (Journal of Environmental Chemical Engineering, 2025)

Nutrients and metal(loid)s in surface sediments of the Chishui River: A DGT-based assessment of the last natural tributary of the upper Yangtze River (China) - Wei Xia; Tian-Xin Zhang; Xue Li; Yanpeng Gao; Richard W. Jordan; Hong Su; Shi-Jun Jiang; Yang-Guang Gu (Environmental Research, 2025)

Solid-state fermentation of distillers grains with Aspergillus pachycristatus for echinocandin B biosynthesis - Jiaxin Tang; Weibing Zhang; Jing Xu; Luyan Sun; Yaqi Dang; Haoyang Li; Liyan Yu; Jing Su; Ting Xue; Rui Guo; Jun Xie; Lei Wang (Bioresource Technology, 2025)

Screening and identification of two repellent active volatiles to Hyphantria cunea - Jin-Yan Lv; Zhao-Jun Meng; Ya-Nan Deng; Yan-Yan Li; Xin-Su Li; Shan-Chun Yan (Journal of Pest Science, 2025)

A Method for Mining Spatial Co-location Patterns Based on Contextual Similarity Among Categories - Xusheng Zhou; Yongbin Tan; Zhonghai Yu; Xiaolong Li; Youneng Su; Jun Wu (Journal of Geovisualization and Spatial Analysis, 2025)

Implications of the application of δ37Cl analysis to a new type of polyhalite potassium ore identified in northeast Sichuan, China - Wen-jun Shang; Kui Su; Kong Li; Yong-sheng Zhang (Carbonates and Evaporites, 2025)
The discovery of a new type of polyhalite potassium ore in the Puguang area of northeast Sichuan Province is expected to alleviate the problem of insufficient potassium resources in China. However, in this high and steep fold belt, tectonic movement has made the sequence division of evaporites difficult; which, this division is an important factor in the study of the genesis of polyhalite. This study analyzed the effect of δ 37 Cl on the salt deformation structure throug h δ 37 Cl distribution in the halite from well CXD1 as an indicator to discussed the genetic mechanism of the new type of polyhalite potassium ore. The following conclusions are drawn: (1) Tectonic activity has a limited influence on the vertical direction of the two or multiple facies of primary sedimentary evaporite dominated by halite components in the plastic dynamic flow process, and the δ 37 C1 value can be used as a reference index in the study of the deformation of salt structures, except for local salt veins and salt in diapirs. (2) The δ 37 C1 values of halite from well CXD1 provide the latest quantitative geochemical data supporting the genetic model of the tectonic events and sedimentary environment influencing the new type of polyhalite potassium ore in the Puguang area of northeast Sichuan; the results indicate that the sedimentary environment featured a wide range of paleowater temperatures, extreme drought and frequent replenishment of marine water sources. (3) Additionally, the low evaporation stage of the Xuanhan area during the late Triassic (the sedimentary period of the fifth constituent of the Jialingjiang formation) about was not conducive to the deposition of soluble K-Mg salt.

Interaction Between Hypoxia-Inducible Factor 1-alpha Gene Polymorphism and Helicobacter pylori Infection on Gastric Cancer in a Chinese Tibetan Population - Su-Hua Li; Yan Li; Meng-Jun Zhang; Qi An; Jia-Nan Tao; Xue-Hong Wang (Biochemical Genetics, 2025)

Construction of the relationship between phytochemicals and gene expression in different Chaenomeles speciosa (Sweet) Nakai cultivars - Ya-Fang Shang; Jun-Hao Miao; Jia Zeng; Si-Qi Sun; Xiao-Long Ni; Zhao-Jun Wei; Yi-Long Ma; Hong-Xing Su; Wen-Bo Bai; Xiang-Li Niu; Wan Zhang (South African Journal of Botany, 2025)

Joule heating of CuO-ZnO/Ni foam catalyst for high H2 production and energy-saving of methanol decomposition: From the performance to mechanism - Xuechen Zhou; Limo He; Chiyu Wang; Yufan Yang; Yanglin Chen; Song Hu; Sam Fong Yau Li; Yifei Sun; Sheng Su; Yi Wang; Jun Xiang (Chemical Engineering Journal, 2025)

Exploring the role of dipole moment at the upper interface of inverted perovskite solar cells through a bi-molecular host–guest strategy - Guoqiang Xu; Imran Muhammad; Danish Khan; Xiaojian Zheng; Yu Zhang; Min Xin; Huaxi Gao; Jiahao Li; Junyu Wang; Di Lu; Shehzad Ahmed; Peng You; et al. (Chemical Engineering Journal, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

A dual-cycle DNA walker sensor for sensitive clinical detection of microRNAs - Yu Han; Xudan Shen; Haihong Hu; Su Zeng; Jun Zhe Min; Jiabin Li; Sheng Cai (Analytica Chimica Acta, 2025)

Stalagmite multi-proxy records reveal spatial complexity of precipitation and monsoon variability in China over past 60 years - Yan-Xia Xue; Yao Wu; Chao-Jun Chen; Tao Fan; Huai Su; Han-Ying Li; Hai Cheng; Jian-Jun Yin; Jun-Yun Li; You-Feng Ning; Ting-Yong Li (Quaternary Science Reviews, 2025)

In-situ nitrogen fixation during sludge pyrolysis integrated with biomass gasification process - Aishu Li; Hengda Han; Liping Du; Zhijie Gong; Song Hu; Kai Xu; Jun Xu; Long Jiang; Yi Wang; Sheng Su; Jun Xiang (Journal of Environmental Management, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Responses of cotton growth, physiology, and soil properties to polyethylene microplastics in arid areas - Chengcheng Wu; Wenhao Su; Zailei Yang; Deqiang Li; Linzhu Gu; Xinyue Chen; Yang Hu; Xinping Zhu; Jun Li; Hongtao Jia; Xingwang Ma (Environmental Geochemistry and Health, 2025)

Coastal redox shifts over the past 167 years and preservation of total organic carbon and total nitrogen - Yang-Guang Gu; Hai-Song Li; Hong Su; Richard W. Jordan; Rui-Ze Liang; Shi-Jun Jiang (Marine Pollution Bulletin, 2025)

From micropores to mechanical strength: Fabrication and characterization of edible corn starch-sodium alginate double network hydrogels with Ca2+ cross-linking - Chun-yan Su; Dong Li; Li-jun Wang (Food Chemistry, 2025)

Green extraction of α-nitroso-β-naphthol from wastewater using hydrophobic deep eutectic solvents: A comprehensive study of efficiency and mechanism - Jie Qian; Ying-hua Li; Di Luo; Si-nan Liu; Fei Su; Jun-xiang Wang (Environmental Pollution, 2025)

Constructing robust multifunctional coating on wearable nylon/cotton blend fabrics for human thermal management, motion monitoring, fire safety, and water repellency - Jian Liu; Xiaowei Su; Qinyong Liu; Xinyu Cui; Hongfei Li; Xiaoyu Gu; Jun Sun; Sheng Zhang (Chemical Engineering Journal, 2025)

Micro-mechanism of basal stresses in steady rock-ice mixture flows: Insights from 2D DEM simulations - Quan Zhang; Li-jun Su; Zhi-bo Dong; Yong-liang Pan (Cold Regions Science and Technology, 2025)

Light iron isotopes in high-silica granites record fluid evolution in magmatic-hydrothermal systems - Qi-Wei Li; Qiang Wang; Lin Ma; Andrew C. Kerr; Jing-Jing Fan; Jun-Hong Zhao; Hai-Ou Gu; Wei Wang; Zhi-Kun Su (Geochimica et Cosmochimica Acta, 2025)

The trojan horse strategy in T-ALL therapy by engineering T-ALL-derived exosomes for targeted delivery of Isoliquiritigenin to the bone marrow to conquer Drug-Resistant T-ALL in PDX model - Yong Liu; Lindi Li; Cheng Ouyang; Zefan Du; Su Liu; Hailin Zou; Chunmou Li; Junbin Huang; Yucai Cheng; Mengyao Tian; Tianwen Li; Jiani Mo; et al. (Chemical Engineering Journal, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

An in-depth understanding of the role and mechanisms of T cells in immune organ aging and age-related diseases - Yudai Xu; Zijian Wang; Shumin Li; Jun Su; Lijuan Gao; Junwen Ou; Zhanyi Lin; Oscar Junhong Luo; Chanchan Xiao; Guobing Chen (Science China Life Sciences, 2025)

Sex-linked DNA marker screening and characterization in albino northern snakehead (Channa argus var.) via third-generation sequencing and pool resequencing - Shengfei Dai; Mimi Chen; Shuqing Zheng; Jian Su; Jun Wu; Linqiang Han; Chaowei Zhou; Yuanchao Zou; Deshou Wang; Minghui Li (Aquaculture, 2025)

Enhanced biofilm-dependent biogas upgrading from waste activated sludge fermentation liquor in microbial electrolysis cells - Lei Li; Lezhu Su; Jun Gao; Shiyu Liu; Shijie Yuan; Nan Zhou; Zhi Zhou; Dongdong Wang; Yan Zhou; Xiaohu Dai (Water Research, 2025)

Occurrence characteristics, removal efficiencies and potential health risks of typical viruses in rural domestic sewage: A review - Yingming Zhu; Su Xu; Yu Zhou; Xuesong Guo; Yunping Han; Jun Zhan; Lin Li; Junxin Liu (Journal of Water Process Engineering, 2025)

Liquid-solid triboelectric nanogenerator for bubbles real-time detecting - Xianzhang Wang; Yixing He; Jiaqi Shao; Yuan Liu; Liran Ma; Buzhen Su; Ruoling Deng; Mingxin Hou; Ge Chen; Jun Li (Chemical Engineering Journal, 2025)

Spin-state regulation of heteronuclear Cu-Co dual-atomic sites via tuning electronic asymmetry for enhanced oxygen reduction - Heng Wang; Xinzhi Zhou; Jiaxin Su; Zixian Liu; Bingbing Xiao; Long Yang; Jun Wang; Yuanli Li; Xunyu Lu; Xiaofeng Zhu (Chemical Engineering Journal, 2025)

Factors affecting the different growth rates of PM2.5：Evidence from composition variation, formation mechanisms, and importance analysis of water-soluble inorganic ions with case study in northern China - Huan Li; Ting Zhang; Hui Su; Sui Xin Liu; Ying Qiang Shi; Lu Yao Wang; Dong Dong Xu; Jia Mao Zhou; Zhu Zi Zhao; Qi Yuan Wang; Steven Sai Hang Ho; Yao Qu; et al. (Atmospheric Environment, 2025)

Unveiling the genetic architecture of barley embryo: QTL mapping, candidate genes identification and its relationship with kernel size and early vigour - Xiaoxia Chen; Zhouyang Su; Yunpu Zheng; Cong Li; Jun Ma; Jian Ma; Fusun Shi; Haiyan Hu; Chunji Liu; Zhi Zheng (Theoretical and Applied Genetics, 2025)
Keymessage In this first QTL mapping study of embryo size in barley, novel and stable QTL were identified and candidate genes underlying a significant locus independent of kernel size were identified based on orthologous analysis and comparison of the whole-genome assemblies for both parental genotypes of the mapping population. Embryo, also known as germ, in cereal grains plays a crucial role in plant development. The embryo accounts for only a small portion of grain weight but it is rich in nutrients. Larger embryo translates to a more nutritious grain and larger store of energy reserves, which can benefit seed germination and seedling establishment. However, reports on quantitative trait loci (QTL) affecting embryo size in barley is rare. To understand the genetic basis of embryo size in barley, a population consisting of 201 F9 recombination inbred lines (RILs) was assessed in four environments. Three regions affecting various characteristics of embryo size including embryo length (EL), embryo width (EW) and embryo area (EA) were consistently identified. They located on chromosomes 2H, 4H and 7H, respectively. Among them, the QTL on 7H was not significantly affected by kernel size. Phenotypic variances explained by this QTL for EL, EW and EA were 11.8%, 9.3% and 12.7%, respectively. Taken advantage of the available genomic assemblies of the two parental genotypes, candidate genes for this locus on 7H were identified. In addition, significant correlations between embryo size and early vigour and kernel traits were detected. To our knowledge, the present study is for the first time reporting QTL conferring embryo size by directly measuring the characteristics as quantitative trait in barley, which would broaden our understanding of the genetic basis of barley embryo size and offer valuable targets for future breeding programmes.

Identification of genetic loci and candidate genes underlying Fusarium crown rot resistance in wheat - Yuqing Su; Xiangru Xu; Yunqiao Wang; Tongzhu Wang; Jiazheng Yu; Jiatian Yang; Jinlong Li; Yutian Gao; Yixin Wang; Wei Sang; Cong Li; Xingyi Wang; et al. (Theoretical and Applied Genetics, 2025)

Morphological evolution of the Qingshuigou subaqueous delta of the Yellow River before and after the operation of the Xiaolangdi Reservoir (1997-2007) - Jiarui Zhang; Qing Wang; Chao Zhan; Zilu Li; Yin Cao; Haojian Wang; Zeyang Liu; Limeng Yu; Qiuyu Song; Yan Li; Teng Su; Jun Zhu; et al. (Frontiers in Marine Science, 2024)
The Modern Yellow River Delta has a rich history of geomorphological transformations shaped by frequent avulsions and rapid progradation. However, the delta entered a phase of altered morphodynamics following the construction of the Xiaolangdi Reservoir, which fundamentally restructured sediment transport regimes and seasonal hydrological patterns. These changes have amplified challenges in predicting long-term deltaic evolution under evolving boundary conditions. The Qingshuigou Subaqueous Delta, as a major depositional zone, provides a compelling lens to examine these morphodynamic processes. However, seasonal variations in riverine sand transport fluxes driven by the water-sand regulation scheme that accompanied the construction of the Xiaolangdi Reservoir and its impact on the evolution of the delta front are particularly understudied. This study developed a simplified long-term morphodynamic model of the Qingshuigou Subaqueous Delta to investigate its response to riverine water and sediment discharges from 1997 to 2007. The findings are as follows: (1) The morphological evolution of the Qingshuigou Subaqueous delta has gradually changed from the pattern of “leading edge deposition and localized near-shore erosion” before the construction of the Xiaolangdi Reservoir to the pattern of “enhanced leading edge deposition and increased near-shore erosion” after the construction. (2) The construction of Xiaolangdi Reservoir has weakened the spatial distribution of the erosion process to a certain extent, changing the spatial distribution dominated by the erosion process (63.8% of area) before the construction to the spatial distribution dominated by the accretion process (More than 50% of area) after the construction. (3) The spatial and temporal variability of the incoming sediments leads to a significant coarsening of the grain size of the tidal flats in the southern part of the abandoned delta, which in turn maintains a relatively steady state of the shoreline variability. In contrast, the abandoned sand spit experiences severe erosion and depositional fluctuations due to intensified wave action. (4) The study emphasizes the importance of considering seasonal variations in unsteady discharge in modeling the long-term evolution of the delta. It provides new insights into the spatial and temporal differentiation of the geomorphic equilibrium of the Yellow River Delta and contributes to a broader understanding of delta evolution.

Hybrid biodegradable materials from starch and hydrocolloid: fabrication, properties and applications of starch-hydrocolloid film, gel and bead - Chun-yan Su; Tong Xia; Dong Li; Li-jun Wang; Yong Wang (Critical Reviews in Food Science and Nutrition, 2024)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Sildenafil citrate induces prostatic hyperplasia in BPH model rats and aged rats - Sisi Huang; Dongyan Huang; Xin Su; Rongfu Yang; Congcong Shao; Juan Jiang; Jun Li; Jianhui Wu (Toxicology and Applied Pharmacology, 2024)

Upcycling of molybdenum tailings, coal gangue and slag into sustainable repaired composites by geopolymerization technology: Workability, embodied carbon and mechanical-microstructural development - Jun Li; Shuang Cao; Qian Su; Hesong Jin; Chang Cai; Lingkun Chen; Jianxing Liu; Tuan Ngo (Sustainable Chemistry and Pharmacy, 2024)

Promotion of antibiotic-resistant genes dissemination by the micro/nanoplastics in the gut of snail Achatina fulica - Yan-Mei Da; Xiao-Ru Yang; Ming-Jun Li; Shun-Shun Li; Ze-Ping Gao; Ying Zhang; Jian-Qiang Su; Guo-Wei Zhou (Science of The Total Environment, 2024)

Remediation of multi-metal(loid) contaminated soils using Mn-modified biochar: Mechanistic insights and influencing factors - Jin-Zhou Su; Xiao-Ning Feng; Ping Xiang; Zhao-Lai Guo; Li-Xin Li; Tao Zhang; Jun-Bao Yu (Process Safety and Environmental Protection, 2024)

Polycyclic polyprenylated acylphloroglucinols from the pericarps of Garcinia multiflora champ. ex Benth. with cytotoxic property - Jun Cao; Wen-Yu Lyu; Yujia Zhang; Zhicheng Su; Ting Li; Qingwen Zhang; Lishe Gan; Jin-Jian Lu; Ligen Lin (Phytochemistry, 2024)

Autonomous docking system for UUV based on cooperative guidance of multiple markers: Design and experiment - Junqi Qu; Jirong Xie; Tao Su; Xinguang Li; Jun Zhang; Qi Sun; Huifeng Jiao (Ocean Engineering, 2024)

Novel catalyst-free activation of chlorine by visible light for micropollutant abatement - Ge Zeng; Linqian An; Maoju Jiang; Wenqi Li; Xiangyang Hou; Peng Su; Minchao Liu; Haijun Cheng; Zhiyun Long; Jingxin Yang; Jun Ma; Tao Yang (Journal of Hazardous Materials, 2024)

Facile synthesis of geopolymer-based hierarchical porous materials for efficient adsorption-photocatalysis of dye wastewater - Han Xiao Su; Chan Juan Li; Yao Jun Zhang (Journal of Environmental Chemical Engineering, 2024)

Development of corn starch-sodium alginate emulsion gels as animal fat substitute: Effect of oil concentration - Chun-yan Su; Dong Li; Li-jun Wang; Yong Wang (Food Hydrocolloids, 2024)

Enhanced peracetic acid activation under Far-UVC Radiation: Micropollutant degradation and radical assessment - Tao Yang; Maoju Jiang; Peng Su; Qixiao Lv; Wenqi Li; Chenlong Liu; Bin Zhang; Haochen Zhang; Linlin Zang; Minchao Liu; Jun Ma (Chemical Engineering Journal, 2024)

SOGCN: Prediction of key properties of MR-TADF materials using graph convolutional neural networks - Yingfu Li; Bohua Zhang; Aimin Ren; Dongdong Wang; Jun Zhang; Changming Nie; Zhongmin Su; Luyi Zou (Chemical Engineering Journal, 2024)

Deciphering heart failure: an integrated proteomic and transcriptomic approach with experimental validation - Jun Cao; Zhaohai Su; Bilong Zhang; Jiangyong Yang; Yueting Wang; Ling Huang; Gang Cao; Hui Xie; Xiutong Zhong; Hengqing Zhu; Rengui Jiang; Tian Li; et al. (Functional & Integrative Genomics, 2024)

Bioinformatics Analysis and Experimental Validation of Differential Genes and Pathways in Bone Nonunions - Wei Xiong; Xing-Li Shu; Lv Huang; Su-Qi He; Lang-Hui Liu; Song Li; Zi-Chen Shao; Jun Wang; Ling Cheng (Biochemical Genetics, 2024)

Resistivity tomography based on multichannel electrodes - Fu-yu Jiang; Jiong Ni; Hai-jun Chen; Li-kun Gao; Song Chen; Xian-wei Wu; Zhi-qiang Su; Yao Lei; Ming-hui Dai; Run Han; Jun-kai Yu (Applied Geophysics, 2024)

Ground motion amplification by twin circular tunnels for obliquely incident seismic waves: Effects of saturated poroelastic soil parameters - Jun Zhu; Stavroula Kontoe; Xiaojun Li; Jianwen Liang; Su Chen (Soil Dynamics and Earthquake Engineering, 2024)

Characterization and origin of high-Al chromitites: A case study of chromite deposit in the Kudi ophiolite in the NW Tibetan Plateau - Jian-Guo Liu; Ben-Xun Su; Xia Liu; Wen-Jun Li; Yang Bai; Jian Wang; Xiang-Jie Wen; Shi-Chun Li (Lithos, 2024)

Decoding the Qu-aroma of medium-temperature Daqu starter by volatilomics, aroma recombination, omission studies and sensory analysis - Sheng-Bing Yang; Jun-Jie Fu; Jia-Huan He; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; Zheng-Hong Xu (Food Chemistry, 2024)

Constructing a multifunctional reactive MXene-based additive for micro-crosslinking polyurea elastomer to achieve superior mechanical properties and enhanced fire safety - Qinyong Liu; Xiaowei Su; Jian Liu; Baozhu Wang; Huihui Li; Jun Sun; Hongfei Li; Xiaoyu Gu; Sheng Zhang (Chemical Engineering Journal, 2024)

Durable flame retardant and UV-resistant coating for Poly (ethylene terephthalate) fabric with recyclability and reusability - Yulong Qu; Feng Chen; Xiaowei Su; Jian Liu; Xiaoyu Gu; Hongfei Li; Jun Sun; Peng Qi; Sheng Zhang (Chemical Engineering Journal, 2024)

Fabrication of thermo-responsive microcapsule pesticide delivery system from maleic anhydride-functionalized cellulose nanocrystals-stabilized pickering emulsion template - Jun Li; Chao Wu; Hong-jun Xu; Jia-wei Ding; Yong-jiang Li; Hui Jiang; Hui-fen Su; Sheng Chen; Xin Li; Muhammad Asif Javaid; De-qiang Li (Carbohydrate Polymers, 2024)

Analysis of post-ground settlement induced during twin tunnelling in silty sand - K.K. Pabodha M. Kannangara; Li-Jun Su; Wan-Huan Zhou (Tunnelling and Underground Space Technology, 2024)

Freshwater microconchids from the Tanzhuang Formation (Middle-Late Triassic) in North China - Hao Yang; Yue Su; Hui-Jun Chen; Yi-Ran Cao; Meng-Yang Zhang; Rui Li; Dao-Liang Chu (Palaeoworld, 2024)

Evolution of heavy components in bio-oil during oxidative pyrolysis of cellulose, hemicellulose, and lignin - Yimin Xiong; Xuepeng Wang; Wei Deng; Peiyong Ma; Kai Xu; Jun Xu; Long Jiang; Yi Wang; Sheng Su; Jianlan Li; Song Hu; Jun Xiang (Fuel, 2024)

Phase inversion of bigels tuned by the concentration of soy protein isolate in the binary hydrogel matrix - Ling-Zhi Su; Ying-Xin Chen; Shi-Qi Zhang; Chun Hu; Jun-Bo He; Wei-Nong Zhang; Li-Juan Han (Food Hydrocolloids, 2024)

A reverberating triple AND logic gate nanomachine for intracellular multi-enzyme tracking and MicroRNA detection - Xu Zhu; Jun Zhu; Jin Wang; Guoquan Wu; Tianyu Su; Liying Fan; Junjie Li; Yufan Liu; Dehong Yu; Rongrong Sun; Ning Xin; Fenglei Gao (Chemical Engineering Journal, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

UV light absorption at 370 nm by mineral dust, organic carbon, and elemental carbon in the Himalayas and Tibetan Plateau - Chong-Shu Zhu; Yao Qu; Yue Zhou; Nan Wang; Hong Huang; Ting Zhang; Xiao-Li Su; Jun-Ji Cao (Atmospheric Environment, 2024)

Remediation of cadmium contaminated soil using electrokinetic-phytoremediation system with rotary switching electrodes - Li Fan; Qin Yuan; Qiuyuan Lu; Chunli Zheng; Ruijing Su; Nuo Liu; Jun Wu (Environmental Geochemistry and Health, 2024)

Unraveling the role of Mn(V)/Mn(III) in the enhanced permanganate oxidation under Vis-LED radiation - Jiamin Mai; Ge Zeng; Maoju Jiang; Peng Su; Qixiao Lv; Wenqi Li; Xiangyang Hou; Minchao Liu; Jun Ma; Tao Yang (Science of The Total Environment, 2024)

A pooled mycoviral resource in a strain of Rhizoctonia solani are regulators of fungal virulence - Ya Rong Wang; Jia En Su; Zhi Juan Yang; Jie Zhong; Xiao Gang Li; Yi Chen; Jun Zi Zhu (Pesticide Biochemistry and Physiology, 2024)

Highly efficient hydrogenation of carbonate to methanol for boosting CO2 mitigation - Zhicheng Xie; Zheyi Sun; Bin Shao; Yuanming Zhu; Rongting Ma; Su Li; Jingkun Li; Yanxin Chen; Honglai Liu; Jun Hu (Chemical Engineering Journal, 2024)

Harnessing bimetallic iMWA nanosensitizer to unleash ferroptosis and calcium overload: Unlocking tumor vulnerability for potentiated iMWA therapy against hepatocellular carcinoma - Guanhua Qiu; Duo Wang; Peihan Xie; Zelun Li; Niqiang Zhou; Xiaoqian Zhang; Xiaobo Wang; Jiali Tang; Jun Cao; Junjie Liu; Danke Su (Chemical Engineering Journal, 2024)

A MYB family transcription factor TdRCA1 from wild emmer wheat regulates anthocyanin biosynthesis in coleoptile - Jinlong Li; Chaozhong Zhang; Xiangru Xu; Yuqing Su; Yutian Gao; Jiatian Yang; Chaojie Xie; Jun Ma (Theoretical and Applied Genetics, 2024)

Effects of nanographene oxide on adipose-derived stem cell cryopreservation - Zifei Li; Jun Qi; Su Fu; Jie Luan; Qian Wang (Cell and Tissue Banking, 2024)

Recent advances in hydrogen process safety: Deflagration behaviors and explosion mitigation strategies - Peng Yang; Tao Wang; Yuhuai Sheng; Yingying Yu; Ruikang Li; Bin Su; Fangming Cheng; Jiao Qu; Jun Deng; Zhenmin Luo (Process Safety and Environmental Protection, 2024)

Modified layered double hydroxides by using Fe-rich porous biochar derived from petrochemical wastewater sludge for enhancing heterogeneous activation of peroxymonosulfate towards chloramphenicol degradation - Su Yan; Siqin Li; Sicheng Zhang; Lina Qian; Xiaoyu Yong; Xueying Zhang; Jun Zhou (Journal of Water Process Engineering, 2024)

Assessment of long-term multisource surface and subsurface soil moisture products and estimate methods on the Tibetan Plateau - Pei Zhang; Donghai Zheng; Rogier van der Velde; Jiangyuan Zeng; Xin Wang; Zuoliang Wang; Yijian Zeng; Jun Wen; Xin Li; Zhongbo Su (Journal of Hydrology, 2024)

Contrasting responses of water use efficiency to increasing aridity in alpine shrubs: A modelling perspective - Menglin Su; Ke Yan; Xiangfu Wang; Jiaxin Jin; Yuanhui Li; Wenting Dong; Haikui Li; Jun Lu; Chuanchuan Zhao; Weifeng Wang (Journal of Hydrology, 2024)

Insights into heavy components evolution in the condensed volatiles from amino acids pyrolysis - Hengda Han; Aishu Li; Song Hu; Grzegorz Lisak; Donglin Wang; Xu Kai; Jun Xu; Long Jiang; Yi Wang; Sheng Su; Jun Xiang (Fuel, 2024)

Green, tough, and heat-resistant: A GDL-induced strategy for starch-alginate hydrogels - Chun-yan Su; Dong Li; Weihong Sun; Li-jun Wang; Yong Wang (Food Chemistry, 2024)

Enhancing U(VI) removal from highly acidic wastewater through the synergistic effect of diethylenetriaminepenta(methylenephosphonic) acid and meso-SiO2 on nanosized γ-Fe2O3 - Hong Li; Diyun Chen; Weixing Han; Jun He; Gang Song; Lingjun Kong; Minhua Su (Chemical Engineering Journal, 2024)

Enhanced separation flux and compressive strength for oil-water separation by adding sodium lignosulphonate - Hui Jiang; Jun Li; Chao Wu; Zi-wei Xiong; Jia-wei Ding; Hui-fen Su; Ya-hui Li; Wen-bo Luo; Liu-jie Yuan; Si-yi Lv; Lu-xiang Wang; De-qiang Li (Chemical Engineering Journal, 2024)

Stable dendrite-free Zn electrodeposition triggered by hydrophobic-zincophilic and elastic interface for highly reversible Zn battery anode - Tian Wang; Hao Fu; Shaocong Tang; Weiwei Xiang; Mengrong Li; Jun Kyu Lee; Liangliang Xu; Jae Su Yu (Chemical Engineering Journal, 2024)

Efficacy and safety of dabigatran and rivaroxaban in atrial fibrillation patients with impaired liver function: a multicenter retrospective cohort study - Xinhai Huang; Wenlin Xu; Guilan Wu; Ruijuan Li; Ping Gu; Qiaowei Zheng; Xiumei Liu; Hengfen Dai; Xiangsheng Lin; Yuxin Liu; Xiaoming Du; Jun Su; et al. (European Journal of Clinical Pharmacology, 2024)

Metabolomics analysis of advancing humification mechanism in secondary fermentation of composting by fungal bioaugmentation - Yuyun Wang; Jun Li; Yuan Chang; Su Chang; Yanting Chen; Dan Wei; Ruoqi Li; Yi Zheng; Zitong Kang; Zhen Wu; Peizhen Chen; Yuquan Wei; et al. (Science of The Total Environment, 2024)

Ent-eudesmane sesquiterpenoids with anti-neuroinflammatory activity from the marine-derived fungus Eutypella sp. F0219 - Zhong-Ping Jiang; Rui Su; Meng-Ting Chen; Jun-Yi Li; Han-Yu Chen; Lu Yang; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Wan-Shan Li; Yong Rao; Ling Huang (Phytochemistry, 2024)

Green mechanochemical activation of solid persulfate to remove PAHs in soil: Performance and mechanism - Junke Zhang; Kexiao Han; Wentao Jiao; Peidong Su; Daxuan Wang; Jun Zhu; Mingshan Zhu; Lin Li (Journal of Hazardous Materials, 2024)

Quick measurement method of three components in lignocellulosic biomass based on kinetic mechanism analysis of PT-TGA - Gongxiang Song; Dexin Huang; Aishu Li; Ruochen Li; Song Hu; Kai Xu; Qiangqiang Ren; Hengda Han; Yi Wang; Sheng Su; Jun Xiang (Fuel, 2024)

Curcumin-loaded biomimetic nanosponges for osteoarthritis alleviation by synergistically suppressing inflammation and ferroptosis - Huihui Xu; Su Liu; Yihao Wei; Siyang Cao; Jiapeng Deng; Guoqing Li; Weibei Sheng; Tiantian Qi; Peng Zhang; Jianjing Lin; Jian Weng; Fei Yu; et al. (Chemical Engineering Journal, 2024)

Photo-assisted natural chalcopyrite activated peracetic acid for efficient micropollutant degradation - Linqian An; Xiujuan Kong; Maoju Jiang; Wenqi Li; Qixiao Lv; Xiangyang Hou; Chenlong Liu; Peng Su; Jun Ma; Tao Yang (Water Research, 2024)

Flexible nanofiber composite solar evaporator for simultaneous interfacial evaporation and heavy metal ion adsorption - Qin Su; Jun Yan; Wei Xiao; Yuntao Liu; Lv Li; Junjie Wang; Xuewu Huang; Huaiguo Xue; Jiefeng Gao (Chemical Engineering Journal, 2024)

Potential pathogenic microorganisms in rural wastewater treatment process: Succession characteristics, concentration variation, source exploration, and risk assessment - Jun Zhan; Su Xu; Yingming Zhu; Yunping Han; Lin Li; Junxin Liu; Xuesong Guo (Water Research, 2024)

Antihypertensive treatment during pregnancy induces long-term changes in gut microbiota and the behaviors of the attention deficit hyperactivity disorder offspring - Hong-Bao Li; Meng-Lu Xu; Wen-Jie Xia; Yuan-Yuan Dong; Bo Peng; Qing Su; Xiao-Min Wang; Jia-Yue Yu; Ya-Nan Gao; Jun-Zhe Wu; Meng-Yue Xu; Jin-Bao Yang; et al. (Toxicology and Applied Pharmacology, 2024)

STON2 variations are involved in synaptic dysfunction and schizophrenia-like behaviors by regulating Syt1 trafficking - Yuanlin Ma; Kai Gao; Xiaoxuan Sun; Jinxin Wang; Yang Yang; Jianying Wu; Anping Chai; Li Yao; Nan Liu; Hao Yu; Yi Su; Tianlan Lu; et al. (Science Bulletin, 2024)

Antihyperglycemic effects of triterpenoid saponins from the seeds of Bge - Gui Mei; Jing Xu; Chumao Wen; Yitong Li; Su Chen; Xiaofei Yang; Jun Li; Yu Chen; Guangzhong Yang (Phytochemistry, 2024)

Role of bipyridyl in enhancing ferrate oxidation toward micropollutants - Juan Li; Jiachun Cao; Maoju Jiang; Linqian An; Ge Zeng; Jiamin Mai; Peng Su; Binghua Jing; Mingbao Feng; Zhimin Ao; Jun Ma; Tao Yang (Journal of Hazardous Materials, 2024)

Genesis of the Hujiazhuang apatite-rich carbonatite complex in North China and its implication for the REE fertility of the carbonatite system - Long Huang; Xiaochun Li; Jianhui Su; Xi Zeng; Hongrui Fan; Jun Lan; Tingguang Lan; Kuifeng Yang; Fangfang Hu (Journal of Asian Earth Sciences, 2024)

Tracing material transport during subduction inception: Insights from potassium isotopes in the crustal sequence of the Troodos ophiolite - Qi-Qi Pan; Yan Xiao; Ben-Xun Su; Paul T. Robinson; Wen-Jun Li; Jing Wang; Xia Liu (Geochimica et Cosmochimica Acta, 2024)

Influences of removable gas injection methods on the temperature field and gas composition of the underground coal gasification process - Fa-qiang Su; Jun-nan Yang; Xiao-long He; Meng-jia Dai; Akihiro Hamanaka; Yi- he Yu; Wen Li; Jiao-yuan Li (Fuel, 2024)

Efficiency and power enhancement strategies for methane direct injection argon power cycle engines - Chenxu Wang; Jun Deng; Weiqi Ding; Yongjian Tang; Wenyi Cui; Xiang Su; Liguang Li (Fuel, 2024)

Experimental and mechanistic studies on the thermo-electric synergistic catalytic oxidation of acetone over MnO2/TiO2-Ni foam catalyst - Chong Tao; Limo He; Xuechen Zhou; Yufan Yang; Hanjian Li; Qiangqiang Ren; Song Hu; Kai Xu; Long Jiang; Jun Xu; Sheng Su; Yi Wang; et al. (Chemical Engineering Journal, 2024)

Immediate and delayed effects of environmental temperature on schizophrenia admissions in Liuzhou, China, 2013–2020: a time series analysis - Qian Zhou; Xiaolan Huang; Li Su; Xianyan Tang; Yanli Qin; Yuting Huo; Chun Zhou; Jun Lan; Yue Zhao; Zaifei Huang; Guoguang Huang; Yuhua Wei (International Journal of Biometeorology, 2024)

Generation of tau dephosphorylation-targeting chimeras for the treatment of Alzheimer’s disease and related tauopathies - Jingfen Su; Yue Xiao; Linyu Wei; Huiyang Lei; Fei Sun; Weixia Wang; Jun Yin; Rui Xiong; Shihong Li; Pei Zhang; Ying Zhou; Xiaochuan Wang; et al. (Science Bulletin, 2024)

Monoterpenoid indole alkaloids from Alstonia scholaris and their Toxoplasma gondii inhibitory activity - Pei-Qian Wu; Zhen-Di Liu; Yu-Hao Ren; Jun-Su Zhou; Qun-Fang Liu; Yan Wu; Ji-Li Zhang; Bin Zhou; Jian-Min Yue (Phytochemistry, 2024)

Visible light-enhancing antibacterial ability of gold ions for its application of the prevention and treatment of dentin caries - Kangjing Li; Beibei Xie; Jun Zhou; Chunyun Liang; Cong Liu; Yiwu Qin; Fengyuan Zhou; Xuan He; Zhiyong Chen; Xiaoping Su; Ying Luo; Cuiping Li; et al. (Journal of Cleaner Production, 2024)

Control of nitrogen and odor emissions during chicken manure composting with a carbon-based microbial inoculant and a biotrickling filter - Haorong Zhang; Liqian Ma; Yinchao Li; Su Yan; Zhenye Tong; Yue Qiu; Xueying Zhang; Xiaoyu Yong; Liwen Luo; Jonathan W.C. Wong; Jun Zhou (Journal of Environmental Management, 2024)

Arsenic disturbs neural tube closure involving AMPK/PKB-mTORC1-mediated autophagy in mice - Xiujuan Li; Gexuan Li; Shuo Cui; Yue Hou; Zelin Li; Ziyi Yan; Tingjuan Huang; Taoran Zhao; Hongkai Su; Bingrui Zhou; Juan Zhang; Ruifang Ao; et al. (Food and Chemical Toxicology, 2024)

A new strategy of using periphyton to simultaneously promote remediation of PAHs-contaminated soil and production of safer crops - Su-Xin Li; Xiao-Rong Gao; Jun Yi; Ling-Yun Jia; Jun Ren (Environmental Research, 2024)

KOH-activated biochar and chitosan composites for efficient adsorption of industrial dye pollutants - Xu Su; Xuanming Wang; Ziyi Ge; Zhengrong Bao; Li Lin; Yixuan Chen; Wanning Dai; Yuanyuan Sun; Hechong Yuan; Wen Yang; Jun Meng; Hailong Wang; et al. (Chemical Engineering Journal, 2024)

Gelatin-polyacrylamide double network enhanced polyamidoxime magnetic photothermal composite hydrogel for highly efficient and selective uranium extraction from seawater - Feixiang Gao; Jianwei Bai; Huijun Yan; Shuaiyu Zheng; Shouzheng Su; Junqing Li; Chunhong Zhang; Jun Wang (Chemical Engineering Journal, 2024)

Friction behaviors and flow resistances of rock-ice avalanches - Zhi-bo Dong; Li-jun Su; Bing-li Hu; Shuai-sheng Miao (Cold Regions Science and Technology, 2024)

Ultrafine Ru nanoparticles stabilized by V8C7/C for enhanced hydrogen evolution reaction at all pH - Yanju Long; Yong Shen; Pingping Jiang; Hui Su; Jiahui Xian; Yamei Sun; Jun Yang; Haili Song; Qinghua Liu; Guangqin Li (Science Bulletin, 2024)

Chemical engineering solution for carbon neutrality in cement industry: Tailor a pathway from inevitable CO2 emission into syngas - Bin Shao; Yuanming Zhu; Jun Hu; Yuan Zong; Zhicheng Xie; Su Li; Wenli Du; Meihong Wang; Honglai Liu; Feng Qian (Chemical Engineering Journal, 2024)

Generation of •OH and intermediate manganese species for the efficient removal of micropollutants via photocatalysis of permanganate by indium oxide - Juan Li; Maoju Jiang; Peng Su; Qixiao Lv; Linqian An; Ge Zeng; Xiangyang Hou; Wenqi Li; Chunzhao Chen; Jun Ma; Tao Yang (Chemical Engineering Journal, 2024)

Identification of a novel and plant height-independent QTL for coleoptile length in barley and validation of its effect using near isogenic lines - Shang Gao; Zhouyang Su; Jun Ma; Jian Ma; Chunji Liu; Huihui Li; Zhi Zheng (Theoretical and Applied Genetics, 2024)
Key message This study reported the identification and validation of novel QTL conferring coleoptile length in barley and predicted candidate genes underlying the largest effect QTL based on orthologous analysis and comparison of the whole genome assemblies for both parental genotypes of the mapping population. Abstract Coleoptile length (CL) is one of the most important agronomic traits in cereal crops due to its direct influence on the optimal depth for seed sowing which facilitates better seedling establishment. Varieties with longer coleoptiles are preferred in drought-prone areas where less moisture maintains at the top layer of the soil. Compared to wheat, genetic study on coleoptile length is limited in barley. Here, we reported a study on detecting the genomic regions associated with CL in barley by assessing a population consisting of 201 recombinant inbred lines. Four putative QTL conferring CL were consistently identified on chromosomes 1H, 5H, 6H, and 7H in each of the trials conducted. Of these QTL, the two located on chromosomes 5H and 6H (designated as Qcl.caf-5H and Qcl.caf-6H ) are likely novel and Qcl.caf-5H showed the most significant effect explaining up to 30.9% of phenotypic variance with a LOD value of 15.1. To further validate the effect of this putative QTL, five pairs of near isogenic lines (NILs) were then developed and assessed. Analysis of the NILs showed an average difference of 21.0% in CL between the two isolines. Notably, none of the other assessed morphological characteristics showed consistent differences between the two isolines for each pair of the NILs. Candidate genes underlying the Qcl.caf-5H locus were also predicted by employing orthologous analysis and comparing the genome assemblies for both parental genotypes of the mapping population in the present study. Taken together, these findings expand our understanding on genetic basis of CL and will be indicative for further gene cloning and functional analysis underly this locus in barley.

Simulation of radiation environment and design of multilayer radiation shield for orbital exploration of Jupiter - Jing Su; Zhiyong Wei; Gang Liu; Jun Xu; Tao Fei; Bo Zhou; Yujing Li; Yangyang Pan; Dongdong Gao; Hexiang Han (Advances in Space Research, 2024)

Large-scale functional network connectivity mediates the association between nigral neuromelanin hypopigmentation and motor impairment in Parkinson’s disease - Su Yan; Jun Lu; Yuanhao Li; Hongquan Zhu; Tian Tian; Yuanyuan Qin; Wenzhen Zhu (Brain Structure and Function, 2024)

Insight into the mechanism of nitrogen sufficiency conversion strategy for microalgae-based ammonium-rich wastewater treatment - Hanwu Song; Jingjing Li; Qihui Su; Hongwu Li; Xujie Guo; Shengxi Shao; Liangliang Fan; Peilun Xu; Wenguang Zhou; Jun Qian (Chemosphere, 2024)

Concurrent impacts of polystyrene nanoplastic exposure and Aeromonas hydrophila infection on oxidative stress, immune response and intestinal microbiota of grass carp (Ctenopharyngodon idella) - Zhen Li; Fang Chen; Maochun Wei; Linyong Zhi; Zeliang Su; Yunxiao Chong; Zhengzhong Xiao; Jun Wang (Science of The Total Environment, 2024)

Optimization of a QuEChERS–LC–MS/MS method for 51 pesticide residues followed by determination of the residue levels and dietary intake risk assessment in foodstuffs - Youzhi Su; Jianjiang Lu; Jun Liu; Fang Li; Ning Wang; Hongqin Lei; Xiaofang Shen (Food Chemistry, 2024)

Flow regimes and basal normal stresses in rock–ice avalanches by experimental rotating drum tests - Zhi-bo Dong; Li-jun Su (Cold Regions Science and Technology, 2024)

A novel QTL conferring Fusarium crown rot resistance on chromosome 2A in a wheat EMS mutant - Xiangru Xu; Yuqing Su; Jiatian Yang; Jinlong Li; Yutian Gao; Cong Li; Xingyi Wang; Lulu Gou; Zhi Zheng; Chaojie Xie; Jian Ma; Jun Ma (Theoretical and Applied Genetics, 2024)

Dissecting the genetic basis of Fusarium crown rot resistance in wheat by genome wide association study - Jinlong Li; Shanshan Zhai; Xiangru Xu; Yuqing Su; Jiazheng Yu; Yutian Gao; Jiatian Yang; Zhi Zheng; Baoyun Li; Qixin Sun; Chaojie Xie; Jun Ma (Theoretical and Applied Genetics, 2024)

One-time root-zone fertilization of controlled-release urea increases nitrogen use efficiency while reducing nitrogen loss risk in a ratoon rice field under two irrigation practices - Zijuan Ding; Jintao Li; Fei Huang; Ren Hu; Shaobing Peng; Jianliang Huang; Jun Hou; Jianli Zhou; Chengfang Li; Bing Su; Mingjian Xu (Nutrient Cycling in Agroecosystems, 2024)

Sludge pyrolysis integrated biomass gasification to promote syngas: Comparison of different biomass - Aishu Li; Hengda Han; Kaiyue Zheng; Meng Zhu; Kai Xu; Jun Xu; Long Jiang; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Science of The Total Environment, 2024)

A highly stretchable, adhesive, and antibacterial hydrogel with chitosan and tobramycin as dynamic cross-linkers for treating the infected diabetic wound - Anqi Xu; Nan Zhang; Shixing Su; Hongyu Shi; Daoqiang Lu; Xifeng Li; Xin Zhang; Xin Feng; Zhuohua Wen; Gengwu Ma; Mengshi Huang; Chi Huang; et al. (Carbohydrate Polymers, 2024)

Identification and quantitative analysis of bioactive components from Potentilla kleiniana Wight et Arn with anti HIV-1 proteases activity - Yong Qiang Zhou; Su Mei Li; Xin Wei; Xin Yang; Jun Wei Xiao; Bo Wen Pan; Shou Xia Xie; Ying Zhou; Jian Yang; Ying Wei (Natural Product Research, 2023)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

A new Trapa from the middle Miocene of Zhangpu, Fujian, southeastern China - Xie-Ting Wu; Zi-Xi Wang; Jun-Wu Shu; Su-Xin Yin; Li-Mi Mao; Gong-Le Shi (Palaeoworld, 2023)

Parental exposure to environmental cadmium causes developmental defects in the rare minnow (Gobiocypris rarus) embryos: The association between ROS-mediated oxidative stress and developmental dysfunction - Liangxia Su; Huanhuan Li; Yinrui Wu; Anni Tao; Ning Qiu; Rui Wang; Liu Jun; Jianwei Wang (Journal of Environmental Chemical Engineering, 2023)

Analytical solution for longitudinal seismic response of immersed tunnel connecting artificial islands crossing different strata - Huanzhu Zhou; Shengan Liu; Bin Li; Weiyun Chen; Lei Su; Jun-Jie Zheng; Yewei Zheng (Computers and Geotechnics, 2023)

Metal-organic frameworks (MOFs)-derived Mn2SnO4@C anode based on dual lithium storage mechanism for high-performance lithium-ion capacitors - You-Kang Duan; Zhi-Wei Li; Shi-Chun Zhang; Tong Su; Yan-Fang Ma; Ai-Jun Jiao; Zhen-Hai Fu (Chemical Engineering Journal, 2023)

A chronostratigraphic and biostratigraphic framework for the Yanliao Biota of northeastern China: Implications for Jurassic terrestrial ecosystems and evolution - Yuling Li; Su-Chin Chang; Haichun Zhang; Jun Wang; Rui Pei; Daran Zheng; Yan Fang; Sidney R. Hemming (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Constructing electrochemical sensor using molecular-imprinted polysaccharide for rapid identification and determination of l-tryptophan in diet - Yan-Jun Li; Li-Li Yang; Li Ni; Jia-Min Xiong; Jia-Yuan He; Lian-Di Zhou; Ling Luo; Qi-Hui Zhang; Chun-Su Yuan (Food Chemistry, 2023)

Bacillus licheniformis inoculation promoted humification process for kitchen waste composting: Organic components transformation and bacterial metabolic mechanism - Yuan Chang; Kaiyun Zhou; Tianxue Yang; Xinyu Zhao; Ruoqi Li; Jun Li; Shaoqi Xu; Ziwei Feng; Xiaoyan Ding; Longli Zhang; Xiong Shi; Jing Su; et al. (Environmental Research, 2023)

Impact of urban wind environment on urban building energy: A review of mechanisms and modeling - Pengyu Jie; Meifang Su; Naiping Gao; Yu Ye; Xiaoming Kuang; Jun Chen; Peixian Li; John Grunewald; Xiaoping Xie; Xing Shi (Building and Environment, 2023)

Study on thermal properties of bio-char prepared by photo-thermal pyrolysis - Dexin Huang; Yankui Wang; Gongxiang Song; Song Hu; Hanjian Li; Yanping Zhang; Yi Wang; Sheng Su; Saad A. El-Sayed; Jun Xiang (Biomass and Bioenergy, 2023)

Room-temperature phosphorescence and fluorescence nanocomposites as a ratiometric chemosensor for high-contrast and selective detection of 2,4,6-trinitrotoluene - Weili Kong; Meina Liu; Jinhui Zhang; Hongbo Wu; Yaqin Wang; Qin Su; Qin Li; Jun Zhang; Chengli Wu; Wen-Sheng Zou (Analytica Chimica Acta, 2023)

Effects of pulse-like ground motions on tunnels in saturated poroelastic soil for obliquely incident seismic waves - Jun Zhu; Xiaojun Li; Jianwen Liang; Stavroula Kontoe; Qiumei He; Su Chen (Soil Dynamics and Earthquake Engineering, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Societal benefits and environmental performance of Chinese aquaculture - Congjun Xu; Guohuan Su; Kangshun Zhao; Xianghong Kong; Hongxia Wang; Xiaoqi Xu; Ziqi Li; Min Zhang; Jun Xu (Journal of Cleaner Production, 2023)

Assessing sustainable performance of aquatic species using multiple footprints for comprehensive dietary advice - Congjun Xu; Guohuan Su; Kangshun Zhao; Xiaoqi Xu; Ziqi Li; Min Zhang; Jun Xu (Journal of Cleaner Production, 2023)

Fe-doped hydrochar facilitating simultaneous methane production and pharmaceutical and personal care products (PPCPs) degradation in co-anaerobic digestion of municipal sludge and food waste - Su Yan; Mengyao Wang; Sicheng Zhang; Zhenye Tong; Siqin Li; Xiaoyu Yong; Xueying Zhang; Jun Zhou (Chemical Engineering Journal, 2023)

Free-radical behaviors of co-pyrolysis of low-rank coal and different solid hydrogen-rich donors: A critical review - Lei Wu; Yining Guan; Changcong Li; Lei Shi; Sasha Yang; B. Rajasekhar Reddy; Gan Ye; Qiuli Zhang; Rock Keey Liew; Jun Zhou; R. Vinu; Su Shiung Lam (Chemical Engineering Journal, 2023)

A Multi-Domain Compression Radiative Transfer Model for the Fengyun-4 Geosynchronous Interferometric Infrared Sounder (GIIRS) - Mingyue Su; Chao Liu; Di Di; Tianhao Le; Yujia Sun; Jun Li; Feng Lu; Peng Zhang; Byung-Ju Sohn (Advances in Atmospheric Sciences, 2023)

Biodegradation behavior and digestive properties of starch-based film for food packaging – a review - Chun-yan Su; Dong Li; Li-jun Wang; Yong Wang (Critical Reviews in Food Science and Nutrition, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Seismogenic structures and velocity structure characteristics of middle-north section of red river fault and adjacent areas - Jun Li; Weiwei Wu; Feng Long; Mingjian Liang; Jinrong Su; Xuefen Chen (Journal of Structural Geology, 2023)

Integration of eQTL and GWAS analysis uncovers a genetic regulation of natural ionomic variation in Arabidopsis - Chaoqun Xu; Ling-Yu Song; Ying Zhou; Dong-Na Ma; Qian-Su Ding; Ze-Jun Guo; Jing Li; Shi-Wei Song; Lu-Dan Zhang; Hai-Lei Zheng (Plant Cell Reports, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Integrating predictive modeling techniques with geospatial data for landslide susceptibility assessment in northern Pakistan - Aamir Asghar; Li-jun Su; Bo Zhao; Nadeem Ahmad Usmani (Journal of Mountain Science, 2023)

Moringa oleifera Lam. leaves as new raw food material: A review of its nutritional composition, functional properties, and comprehensive application - Min Yang; Liang Tao; Xin-Rui Kang; Zi-Lin Wang; Ling-Yan Su; Ling-Fei Li; Fan Gu; Cun-Chao Zhao; Jun Sheng; Yang Tian (Trends in Food Science & Technology, 2023)

Association of long-term particulate matter exposure with all-cause mortality among patients with ovarian cancer: A prospective cohort - Yi-Zi Li; Shu-Hong Huang; Su Shi; Wen-Xiao Chen; Yi-Fan Wei; Bing-Jie Zou; Wei Yao; Lu Zhou; Fang-Hua Liu; Song Gao; Shi Yan; Xue Qin; et al. (Science of The Total Environment, 2023)

Blood-based biomarkers for Alzheimer’s disease: a multicenter-based cross-sectional and longitudinal study in China - Feng Gao; Linbin Dai; Qiong Wang; Chang Liu; Kexue Deng; Zhaozhao Cheng; Xinyi Lv; Yan Wu; Ziyi Zhang; Qingqing Tao; Jing Yuan; Shiping Li; et al. (Science Bulletin, 2023)

Transcriptomic analysis of the fat body of resistant and susceptible silkworm strains, Bombyx mori (Lepidoptera), after oral treatment with fenpropathrin - Zi-qin Zhao; Kai-yi Zheng; Yu-tong Zhu; Jun-li Lv; Zhi-hao Su; Xiao-ying Zhang; Wen-qing Lai; Mu-wang Li; Yang-chun Wu; Xue-yang Wang (Pesticide Biochemistry and Physiology, 2023)

Schiff base reaction induced densification of chitosan-derived microporous carbon for compact capacitive energy storage - Jun Zhang; Tingting Tang; Xuemeng Gan; Renlu Yuan; Qiqi Li; Linna Zhu; Nannan Guo; Jiayao Zhu; Yutong Li; Su Zhang; Zhuangjun Fan; Huaihe Song (Chemical Engineering Journal, 2023)

Quantifying source effects based on rainwater δ18O from 10-year monitoring records in Southwest China - Yan-Xia Xue; Jian Zhang; Zhen Su; Yao Wu; Qi-sheng Liang; Ming-Qiang Liang; Xiang-Zhuo Liu; Chao-Jun Chen; Hai-Ying Qiu; Jun-Yun Li; Ting-Yong Li (Applied Geochemistry, 2023)

Circular RNA Circ_0005962 Contributes to Lung Adenocarcinoma Cell Proliferation and Stem Cell Formation Through Sponging of miR-3611 and Modulating CYP24A1 Expression - Wenjing Lu; Zhigao Yu; Jun Liu; Liping Li; Liang Liu; Xiaoju Li; Dan Ye; Shengtian Su (Biochemical Genetics, 2023)

Benzo(a)pyrene regulates chaperone-mediated autophagy via heat shock protein 90 - Min Su; Shuhong Zhou; Jun Li; Nan Lin; Tao Chi; Mengdi Zhang; Xiaoli Lv; Yuxia Hu; Tuya Bai; Fuhou Chang (Toxicology Letters, 2023)

Ball-milled magnetic sludge biochar enables fast aerobic granulation in anoxic/oxic process for the treatment of coal chemical wastewater - Dan Li; Su Yan; Xiaoyu Yong; Xueying Zhang; Jun Zhou (Science of The Total Environment, 2023)

Artemiprinolides A−M, thirteen undescribed sesquiterpenoid dimers from Artemisia princeps and their antihepatoma activity - Li-Hua Su; Wen-Jing Ma; Yun-Bao Ma; Tian-Ze Li; Chang-An Geng; Wei Dong; Xiao-Feng He; Ji-Jun Chen (Phytochemistry, 2023)

Potassium isotope fractionation during granite differentiation and implications for crustal K isotope heterogeneity - Zi-Yi Ding; Shan-Ke Liu; Ben-Xun Su; Wen-Jun Li; Yang Bai; Qi-Qi Pan; Fang-Yang Hu; Kwan-Nang Pang (Lithos, 2023)

Integrated fixed-film activated sludge systems in continuous-flow and batch mode acclimated from low to high aniline concentrations: Performance, mechanism and metabolic pathways - Nan-ping Wu; Qian Zhang; Bin Tan; Meng Li; Bing Lin; Jing He; Jun-hao Su; Hao-nan Shen (Bioresource Technology, 2023)

Application of the metal ions as potential population biomarkers for wastewater-based epidemiology: estimating tobacco consumption in Southern China - Lei Xu; Yu-ting Lu; Dong-feng Wu; Xuan Li; Min Song; Tai-jun Hang; Meng-xiang Su (Environmental Geochemistry and Health, 2023)

Recycling of steel slag as an alkali activator for blast furnace slag: geopolymer preparation and its application in composite cement - Qiang Wang; Hui-li Su; Chuan-ming Li; Xian-jun Lyu (Clean Technologies and Environmental Policy, 2023)

Octyl gallate targeting the 3C-like protease exhibits highly efficient antiviral activity against swine enteric coronavirus PEDV - Mingjun Su; Baishuang Yin; Xiaoxu Xing; Zijian Li; Jiyu Zhang; Shufeng Feng; Lu Li; Feiyu Zhao; Xu Yang; Shiping Yu; Jun Wang; Yongchen Zhang; et al. (Veterinary Microbiology, 2023)

Identification and validation of new MADS-box homologous genes in 3010 rice pan-genome - Weihua Li; Duoxiang Wang; Xiaokun Hong; Jin Shi; Jun Hong; Su Su; Cristopher Reyes Loaiciga; Jing Li; Wanqi Liang; Jianxin Shi; Dabing Zhang (Plant Cell Reports, 2023)

CircFhit Modulates GABAergic Synaptic Transmission via Regulating the Parental Gene Fhit Expression in the Spinal Dorsal Horn in a Rat Model of Neuropathic Pain - Ting Xu; Zhen-Yu Li; Meng Liu; Su-Bo Zhang; Huan-Huan Ding; Jia-Yan Wu; Su-Yan Lin; Jun Liu; Jia-You Wei; Xue-Qin Zhang; Wen-Jun Xin (Neuroscience Bulletin, 2023)

Experimental research and theoretical analysis of flow instability in advanced secondary passive residual heat removal system - Liangguo Li; Jianming Yu; Zongbao Nan; Donghua Lu; Jun Xing; Xianghui Lu; Yingwei Wu; Suizheng Qiu; Guanghui Su; Wenxi Tian; Xiaohang Wu; Jiyong Liu (Annals of Nuclear Energy, 2023)

Carp stocking and climate change are potentially more important factors than nutrient enrichment driving water quality deterioration in subtropical freshwater lakes in China - Haojie Su; Jianfeng Chen; Yun Li; Qingyang Rao; Congqiang Luo; Xuwei Deng; Hong Shen; Renhui Li; Jun Chen; Yuanfeng Sun; Jiamin Pan; Suhui Ma; et al. (Limnology and Oceanography, 2023)
Freshwater lakes across the world have undergone dramatic changes in biological components and water quality over the past several decades. Previous studies focused on potential drivers mainly on nutrient enrichment in the catchment. However, the relative importance of climate change and the top‐down cascade effects of fish stocking on water quality is not fully understood. Here, by compiling 155 lakes data with four periods of field investigation in subtropical lakes in China, we found no significant changes in water total nitrogen and total phosphorus in the past two decades. However, the phytoplankton abundance increased significantly, and the water clarity declined by 44.1%. We further found that carp stocking and climate change are potentially more important than nutrients driving water quality change, which is also evidenced in two lakes (Lake Donghu and Qiandao) with long‐term monitoring histories. Specifically, carp stocking can decrease the water clarity directly by stirring up sediment and indirectly by trophic cascade along the food web. For climatic factors, mean annual temperature (MAT) has a positive effect on phytoplankton abundance, while mean annual precipitation has a negative one, with climates overall having little effect on water clarity. In addition, nutrient enrichment and climate change also have strong interactions with carp stocking, which may enhance the top‐down effects on water quality. Our findings highlight that either MAT or carp stocking may become an overwhelming driver of water clarity decline, which provides new insights into the conservation strategy for water quality management in the subtropical lakes in China.

2,4-Dinitrotoluene (2,4-DNT) exposure induces liver developmental damage and perturbs lipid metabolism and oxygen transport gene expression in zebrafish (Danio rerio) - Liangxia Su; Hang Sha; Jun Liu; Le Yu; Huanhuan Li; Rui Wang (Environmental Science and Pollution Research, 2023)

Development and characterization of 50 SNP markers in three watersheds populations of Xenocypris davidi - Chaoqun Su; Chenxi Tan; Liangjie Zhao; Xinliang Peng; Jun Liu; Haolong Li; Xusheng Guo (Conservation Genetics Resources, 2023)

First report of Fusarium foetens causing root rot on lavender (Lavandula angustifolia) in China - Xue-Jun Wei; Bing-Guo Jia; Xing Wang; Nan-Yang Li; Su-Na Wang; Li Li; Ai Zhang; Hao-Tian Zhang; Li-Ping Wang (Journal of Plant Pathology, 2023)

Rapid change of erosion-deposition evolution in the Minjiang estuary, Southeast China - Xiaohe Lai; Yuebao Hou; Jianping Jia; Cheng Chen; Yan Su; Jun Jiang; Jing Chen; Maotian Li; Yan Liu (Ocean & Coastal Management, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Heavy metals in riverine/estuarine sediments from an aquaculture wetland in metropolitan areas, China: Characterization, bioavailability and probabilistic ecological risk - Hai-Song Li; Yang-Guang Gu; Rui-Ze Liang; Ya-Su Wang; Richard W. Jordan; Liang-Gen Wang; Shi-Jun Jiang (Environmental Pollution, 2023)

Investigating the location of zone prone to reactivation due to water saturation on landslide debris using electrical resistivity tomography - Faheem Ullah; Li-Jun Su; Elena S. Kazantseva; Mehtab Alam (Bulletin of Engineering Geology and the Environment, 2023)

Effects of different cage sizes and nest settings on laying hen nesting behavior and the proportion of dirty eggs in furnished cages - Hanqing Sun; Peng Zhao; Yingying Su; Qian Zhao; Xiang Li; Jun Bao (Applied Animal Behaviour Science, 2023)

Sugarcane leaf-stalk separating technology: A critical review - Peng Huo; Shaochun Ma; Chenyang Su; Zhengliang Ding; Weiqing Li; Jun Qian; Lingfeng Li; Yechen Li; Baocheng Zhou; Chong Peng; Wenzhi Li (Biosystems Engineering, 2023)

Associations of polycyclic aromatic hydrocarbons, water-soluble ions and metals in PM2.5 with liver function: Evidence from schizophrenia cohort - Weizhuo Yi; Jun Cheng; Jian Song; Rubing Pan; Yunfeng Liang; Xiaoni Sun; Yuxuan Li; Yudong Wu; Shuangshuang Yan; Xiaoyu Jin; Lu Mei; Jian Cheng; et al. (Science of The Total Environment, 2023)

Two new dicyclic C-geranylflavanones isolated from Paulownia fortunei and their cytotoxicity - Wei-guo Liu; Cheng-mei Xiao; Jun Li; Su-ying Wu; Wen-chao Zhang; Ling-tao Kong; Wen-Zhao Tang; Xian-hui Jia (Phytochemistry Letters, 2023)

FeNi3 foam as cathode catalyst in electrocatalytic peroxydisulfate system for enhanced Hg0 removal from simulated flue gas - Qianqian Zhang; Anchao Zhang; Hao Li; Xinmin Zhang; Zhijun Sun; Yanyang Mei; Jun Xiang; Sheng Su; Zengqiang Tan; Hao Lu (Journal of Environmental Chemical Engineering, 2023)

Transformation of hydroxylamine to nitrosated and nitrated products during advanced oxidation process - Zi-jun Dong; Cheng-chun Jiang; Yue Zhou; Jie-bin Duan; Li-hong Wang; Su-yan Pang; Jin Jiang; Xiao-hui Sun (Journal of Hazardous Materials, 2023)

Assessment of greenhouse gases emissions and intensity from Chinese marine aquaculture in the past three decades - Congjun Xu; Guohuan Su; Kangshun Zhao; Huan Wang; Xiaoqi Xu; Ziqi Li; Qiang Hu; Jun Xu (Journal of Environmental Management, 2023)

The influence of CO2 huff and puff in tight oil reservoirs on pore structure characteristics and oil production from the microscopic scale - Xing Huang; Xingyu Wang; Mengqing He; Yu Zhang; Zezhong Su; Xiang Li; Weipeng Yang; Jun Lu (Fuel, 2023)

Physics-guided genetic programming for predicting field-monitored suction variation with effects of vegetation and atmosphere - Zhi-Liang Cheng; K.K. Pabodha M. Kannangara; Li-Jun Su; Wan-Huan Zhou; Chen Tian (Engineering Geology, 2023)

Erratum to: Rigid block characteristics on subaerial landslide-tsunamis using a 3D coupled Eulerian-Lagrangian model - Yi-ding Bao; Jian-ping Chen; Li-jun Su; Xin Zhou; Cheng-shan Yin (Journal of Mountain Science, 2023)

MUSER and IPS telescopes for solar and space weather observations - Yihua Yan; Wei Wang; Linjie Chen; Fei Liu; Jin Fan; Zhijun Chen; Lihong Geng; Chengming Tan; Suli Ma; Sha Li; Cang Su; Jing Du; et al. (Advances in Space Research, 2023)

Abnormal fatty acid metabolism and ceramide expression may discriminate myocardial infarction from strangulation death: A pilot study - Song-Jun Wang; Bing-Rui Liu; Fu Zhang; Ya-Ping Li; Xiao-Rui Su; Chen-Teng Yang; Bin Cong; Zhi-Hua Zhang (Tissue and Cell, 2023)

Microbial-induced calcium carbonate precipitation: Influencing factors, nucleation pathways, and application in waste water remediation - Yu Liu; Amjad Ali; Jun-Feng Su; Kai Li; Rui-Zhu Hu; Zhao Wang (Science of The Total Environment, 2023)

Effects of fine ambient particulate matters on de novo hypertensive disorders of pregnancy and blood pressure before 20 weeks - Zhichao Yuan; Qin Li; Tao Su; Jie Yang; Junjun Chen; Yuanzhou Peng; Shuang Zhou; Heling Bao; Shusheng Luo; Hui Wang; Jue Liu; Na Han; et al. (Environmental Research, 2023)

IFI44L as a novel epigenetic silencing tumor suppressor promotes apoptosis through JAK/STAT1 pathway during lung carcinogenesis - Yong Zeng; Hong-qiang Chen; Zhe Zhang; Jun Fan; Jing-zhi Li; Shi-meng Zhou; Na Wang; Su-peng Yan; Jia Cao; Jin-yi Liu; Zi-yuan Zhou; Wen-bin Liu (Environmental Pollution, 2023)

Total petroleum hydrocarbons and influencing factors in co-composting of rural sewage sludge and organic solid wastes - Su Xu; Jun Zhan; Lin Li; Yingming Zhu; Junxin Liu; Xuesong Guo (Environmental Pollution, 2023)

Rigid block characteristics on subaerial landslide-tsunamis using a 3D coupled Eulerian-Lagrangian model - Yi-ding Bao; Jian-ping Chen; Li-jun Su; Xin Zhou; Cheng-shan Yin (Journal of Mountain Science, 2023)

This is what we know: Assessing the stock status of the data-poor skipjack tuna (Katsuwonus pelamis) fishery in the South China Sea - Kui Zhang; Jun Zhang; Peng Zhang; Li Su; Xiaofan Hong; Yongsong Qiu; Zuozhi Chen (Frontiers in Marine Science, 2023)
Skipjack tuna ( Katsuwonus pelamis ) is a highly migratory species of significant value in global marine fisheries. The South China Sea (SCS) is the largest marginal sea in the northwestern Pacific Ocean, and many tuna and tuna-like species occur within it. Although a recent Western and Central Pacific Fisheries Commission report identified skipjack tuna in the western and central Pacific to be sustainably fished, the exploitation status of skipjack tuna in the SCS is still unclear, due to limited data. We apply two data-poor methods, length-based Bayesian biomass estimation (LBB) and length-based spawning potential ratio (LBSPR), to assess the status of skipjack tuna stock in the SCS. We use electronic length frequency analysis to estimate von Bertalanffy growth parameters (asymptotic length L inf and growth coefficient K ) to serve as priors for LBB and LBSPR estimation. Estimates are calculated for SCS skipjack tuna L inf (68.3 cm), K (0.325 year −1 ), natural mortality (0.49 year −1 ) and mean fork length at 50% sexual maturity (36.7 cm). LBB analysis reveals the estimated relative stock size (0.29) indicates that the SCS skipjack tuna stock maybe heavily overfished. LBSPR analysis reveals the estimated spawning potential ratio for this fishery to be 3%, which is significantly below the limit reference point of 20%. Accordingly, for the SCS skipjack tuna stock we identify a need to reduce fishing mortality by controlling fishing effort and increasing catchable size.

Radical chemistry, degradation mechanism and toxicity evolution of BPA in the UV/chlorine and UV/H2O2 - Ying Cao; Jun Yao; Tatjana Šolević Knudsen; Wancheng Pang; Junjie Zhu; Bang Liu; Hao Li; Miaomiao Li; Jianchao Su (Chemosphere, 2023)

Multi-index assessment of heavy metal contamination in surface sediments of the Pearl River estuary intertidal zone - Rui-Ze Liang; Yang-Guang Gu; Hai-Song Li; Yan-Jie Han; Jie Niu; Hong Su; Richard W. Jordan; Xiang-Tian Man; Shi-Jun Jiang (Marine Pollution Bulletin, 2023)

DNA methylation reprogramming provides insights into light-induced anthocyanin biosynthesis in red pear - Hai-Nan Liu; Qun Shu; Kui Lin-Wang; Richard V. Espley; Andrew C. Allan; Mao-Song Pei; Xiao-Long Li; Jun Su; Jun Wu (Plant Science, 2023)

Thermodynamic characteristics of methane hydrate formation in high-pressure microcalorimeter under different reaction kinetics - Juan Fu; Jia-Mei Mo; Shi-Jun Liu; Wen-Zhe Yi; Yi-Song Yu; Neng-You Wu; Xiao-Li Chen; Qiu-Cheng Su; Xiao-Sen Li (Fuel, 2023)

Thermal behavior, synergistic effect and thermodynamic parameter evaluations of biomass/plastics co–pyrolysis in a concentrating photothermal TGA - Abdulmajid Abdullahi Shagali; Song Hu; Hanjian Li; Huanying Chi; Haoran Qing; Jun Xu; Long Jiang; Yi Wang; Sheng Su; Jun Xiang (Fuel, 2023)

The impact of three related emission industries on regional atmospheric chlorinated paraffins pollution - Qilu Li; Shanshan Jiang; Yajing Li; Jingjing Su; Jingfang Shangguan; Mengdi Zhan; Yan Wang; Xianfa Su; Jun Li; Gan Zhang (Environmental Pollution, 2023)

Green double crosslinked starch-alginate hydrogel regulated by sustained calcium ion-gluconolactone release for human motion monitoring - Chun-yan Su; Dong Li; Li-jun Wang; Yong Wang (Chemical Engineering Journal, 2023)

Ultrastable and ultrafast 3D charge–discharge network of robust chemically coupled 1 T-MoS2/Ti3C2 MXene heterostructure for aqueous Zn-ion batteries - Fei Long; Qixiang Zhang; Junjie Shi; Li Wen; Yonghui Wu; Ziqi Ren; Zunyu Liu; Yixin Hou; Ke Mao; Ke Niu; Nishuang Liu; Zhi Zhang; et al. (Chemical Engineering Journal, 2023)

Structural and functional alterations within the Papez circuit in subacute stroke patients - Su Yan; Yuanhao Li; Jun Lu; Tian Tian; Guiling Zhang; Yiran Zhou; Di Wu; Shun Zhang; Wenzhen Zhu (Brain Imaging and Behavior, 2022)

Geomorphic and tectonic controls of landslides induced by the 2022 Luding earthquake - Bo Zhao; Kai-heng Hu; Zong-ji Yang; Qiao Liu; Qiang Zou; Hua-yong Chen; Bo Zhang; Wei-feng Zhang; Lei Zhu; Li-jun Su (Journal of Mountain Science, 2022)

CircTMEM59 Serves as miR-410-3p Sponge to Inhibit the Proliferation and Metastasis of Colorectal Cancer by Regulating HOXD8 - Jun Liu; Juyuan Li; Yu Su; Zhen Ma; Shun Yu; Xiaoling Meng (Biochemical Genetics, 2022)

Enhancing extracellular electron transfer through selective enrichment of Geobacter with Fe@CN-modified carbon-based anode in microbial fuel cells - Xiao-Long Cheng; Qiang Xu; Qian-Wen Yang; Rui-Rui Tian; Biao Li; Su Yan; Xue-Ying Zhang; Jun Zhou; Xiao-Yu Yong (Environmental Science and Pollution Research, 2022)

Comparative transcriptome analyses identify genes involved into the biosynthesis of forsythin and forsythoside A in Forsythia suspensa - Wang Jun Yuan; Su Ping Zhang; Zhi Yin He; Yan Xia He; She Qi He; Li Jun Liu; Xin Sun; Qin Li (Functional & Integrative Genomics, 2022)

Circ_0009910 Serves as miR-361-3p Sponge to Promote the Proliferation, Metastasis, and Glycolysis of Gastric Cancer via Regulating SNRPA - Jun Liu; Juyuan Li; Yu Su; Zhen Ma; Shun Yu; Yiming He (Biochemical Genetics, 2022)

Influence of pyrolysis temperature on sludge biochar: the ecological risk assessment of heavy metals and the adsorption of Cd(II) - Menglan Wu; Bo Liu; Jun Li; Xintai Su; Weizhen Liu; Xiaoqin Li (Environmental Science and Pollution Research, 2022)

Landslide stability investigation and subsurface deformation mapping by optimizing low-frequency GPR: A mega rainfall susceptible landslide case study (Gilgit Baltistan, Pakistan) - Faheem Ullah; Li-Jun Su; Mehtab Alam; Li Cheng; Mohib Ur Rehman; Aamir Asghar; Gulfam Hussain (Bulletin of Engineering Geology and the Environment, 2022)

Genetic basis underlying tiller angle in rice (Oryza sativa L.) by genome-wide association study - Shaoxing Bai; Jun Hong; Su Su; Zhikang Li; Wensheng Wang; Jianxin Shi; Wanqi Liang; Dabing Zhang (Plant Cell Reports, 2022)

Effect of absolute humidity on influenza activity across different climate regions in China - Li Qi; Tian Liu; Yuan Gao; Qin Li; Wenge Tang; Dechao Tian; Kun Su; Yu Xiong; Jun Yang; Luzhao Feng; Qiyong Liu (Environmental Science and Pollution Research, 2022)

Does green credit policy promote the green innovation efficiency of heavy polluting industries?—empirical evidence from China’s industries - Su Li; Wei Zhang; Jun Zhao (Environmental Science and Pollution Research, 2022)

Influence of particle breakage on the isotropic compressibility of sands - Fang-wei Yu; Li-jun Su; Xiong-zhi Peng (Journal of Mountain Science, 2022)

Erratum to: Estimating the maximum impact force of dry granular flow based on pileup characteristics - Si-you Xiao; Li-jun Su; Yuan-jun Jiang; Alam Mehtab; Cheng Li; Dao-chuan Liu (Journal of Mountain Science, 2022)

Aquapteridospora jiangxiensis, a new aquatic hyphomycetous fungus from a freshwater habitat in China - Su-Qin Peng; Yu-Lin Liu; Jun-En Huang; Xiao-Hong Li; Xin-Yi Yan; Hai-Yan Song; Yang Gao; Zhi-Jun Zhai; Yuan-Qiu Liu; Dian-Ming Hu (Archives of Microbiology, 2022)

Neurovascular abnormalities in retinopathy of prematurity and emerging therapies - Chang Dai; Jun Xiao; Chenguang Wang; Wei Li; Guanfang Su (Journal of Molecular Medicine, 2022)

Qipengyuania thermophila sp. nov., isolated from a Chinese hot spring - Zi-Yu Zhao; Ting-Ting Xia; Jian-Yu Jiao; Lan Liu; Qing-Yang Su; Meng-Meng Li; Ai-Ping Lv; Yu-Ting Ouyang; Wen-Jun Li; Hong Ming (Archives of Microbiology, 2022)

Natural component plumbagin as a potential antibacterial agent against Streptococcus agalactiae infection - Ai‐Guo Huang; Lin‐Jun Su; Wei‐Hao He; Fa‐Li Zhang; Chao‐Shuai Wei; Ying‐Hui Wang (Journal of Fish Diseases, 2022)
Streptococcus agalactiae , also known as Group B Streptococcus (GBS), can infect humans, terrestrial animals and fish. The emergence of bacterial resistance of S. agalactiae to antibiotics leads to an urgent need of exploration of new antimicrobial agents. In the study, the antibacterial activity of natural component plumbagin (PLB) against S. agalactiae was investigated in vitro and in vivo. The results showed that the minimal inhibitory concentration (MIC) of PLB against S. agalactiae was 8 mg/L. The growth curve assay revealed that PLB could inhibit the growth of S. agalactiae . In addition, the time‐killing curve showed that S. agalactiae was killed almost completely by 2‐fold MIC of PLB within 12 h. Transmission electron microscopy results showed obvious severe morphological destruction and abnormal cells of S. agalactiae after treated with PLB. The pathogenicity of S. agalactiae to zebrafish was significantly decreased after preincubation with PLB for 2 h in vitro, further indicating the bactericidal activity of PLB. Interestingly, PLB could kill S. agalactiae without inducing resistance development. Furthermore, pretreatment and post‐treatment assays suggested that PLB also exhibited the antibacterial activity against S. agalactiae infection in vivo by effectively reducing the bacterial load and improving the survival rate of S. agalactiae ‐infected zebrafish. In summary, PLB had potent antibacterial activity against S. agalactiae in vitro and in vivo, and it could be an excellent antimicrobial candidate to prevent and control S. agalactiae infection.

Effects of Involuntary and Voluntary Exercise in Combination with Acousto-Optic Stimulation on Adult Neurogenesis in an Alzheimer's Mouse Model - Wan-yi Li; Jun-yan Gao; Su-Yang Lin; Shao-tao Pan; Biao Xiao; Yu-tao Ma; Kai Xie; Wei Shen; Zhi-tao Liu; Guang-yu Li; Jie-jie Guo; Qin-wen Wang; et al. (Molecular Neurobiology, 2022)

Chromosome-Scale Assembly and Characterization of the Albino Northern Snakehead, Channa argus var. (Teleostei: Channidae) Genome - Chaowei Zhou; Yan Li; Yan Zhou; Yu Zou; Dengyue Yuan; Xingxing Deng; Luo Lei; Jian Su; Chengke Zhu; Hua Ye; Hui Luo; Guangjun Lv; et al. (Frontiers in Marine Science, 2022)
Northern snakehead, Channa argus ( C. argus ), is an important economic and ecological fish species. The wild population of the species was sharply declined in the last decade. A high-quality reference genome could lay a solid foundation for the genetic and conservation studies for C. argus . In this work, we report a chromosomal genome assembly with PacBio and Hi-C technology using the albino northern snakehead, a color variety of C. argus . A 644.1-Mb genome with 24 chromosomes was obtained with a contig and scaffold N50 of 11.78 and 27.8 Mb, respectively. We inferred that C. argus diverged from A. testudineus around 85.6 million years ago. 514 expanded gene families and 214 positively selected genes were identified in the C. argus genome. The chromosome-level genome provides a valuable high-quality genomic resource for population, as well as genetic and evolutionary studies for C. argus and other species in Channidae.

Dissection of the practical soybean breeding pipeline by developing ZDX1, a high-throughput functional array - Rujian Sun; Bincheng Sun; Yu Tian; Shanshan Su; Yong Zhang; Wanhai Zhang; Jingshun Wang; Ping Yu; Bingfu Guo; Huihui Li; Yanfei Li; Huawei Gao; et al. (Theoretical and Applied Genetics, 2022)
Key message We developed the ZDX1 high-throughput functional soybean array for high accuracy evaluation and selection of both parents and progeny, which can greatly accelerate soybean breeding. Abstract Microarray technology facilitates rapid, accurate, and economical genotyping. Here, using resequencing data from 2214 representative soybean accessions, we developed the high-throughput functional array ZDX1, containing 158,959 SNPs, covering 90.92% of soybean genes and sites related to important traits. By application of the array, a total of 817 accessions were genotyped, including three subpopulations of candidate parental lines, parental lines and their progeny from practical breeding. The fixed SNPs were identified in progeny, indicating artificial selection during the breeding process. By identifying functional sites of target traits, novel soybean cyst nematode-resistant progeny and maturity-related novel sources were identified by allele combinations, demonstrating that functional sites provide an efficient method for the rapid screening of desirable traits or gene sources. Notably, we found that the breeding index (BI) was a good indicator for progeny selection. Superior progeny were derived from the combination of distantly related parents, with at least one parent having a higher BI. Furthermore, new combinations based on good performance were proposed for further breeding after excluding redundant and closely related parents. Genomic best linear unbiased prediction (GBLUP) analysis was the best analysis method and achieved the highest accuracy in predicting four traits when comparing SNPs in genic regions rather than whole genomic or intergenic SNPs. The prediction accuracy was improved by 32.1% by using progeny to expand the training population. Collectively, a versatile assay demonstrated that the functional ZDX1 array provided efficient information for the design and optimization of a breeding pipeline for accelerated soybean breeding.

An evaluation method for internal erosion potential of gravelly soil based on particle size distribution - Qin Zhu; Li-jun Su; Zhen-yu Liu; Bin Wang (Journal of Mountain Science, 2022)

Circ_0007031 Silencing Inhibits Cell Proliferation and Induces Cell Apoptosis via Downregulating MELK at a miR-485-3p-Dependent Way in Colorectal Cancer - Shengtian Su; Wenjing Lu; Jun Liu; Liping Li; Liang Liu; Xiaoju Li; Dan Ye; Zhigao Yu (Biochemical Genetics, 2022)

Two new amide glycosides with anti-inflammatory activity from the leaves of Streblus ilicifolius (Vidal) Corner - Yan Huang; Xishan Huang; Guobiao Tian; Wenxiu Zhang; Shanshan Su; Xia Xu; Jun Li; Buming Liu (Natural Product Research, 2022)

Is Zooplankton Body Size an Indicator of Water Quality in (Sub)tropical Reservoirs in China? - Li Wang; Jun Chen; Haojie Su; Xufa Ma; Zhixu Wu; Hong Shen; Jia Yu; Jiarui Liu; Yao Wu; Guangyi Ding; Ping Xie (Ecosystems, 2022)

Isolation and characterization of 34 SNP markers in Acipenser baerii - Quan Gong; Qingzhi Li; Jiahua Sun; Yu Xiao; Xutao Su; Guangxun Liu; Jun Du; Jue Lin (Conservation Genetics Resources, 2022)

Identification and characterization of QTL for spike morphological traits, plant height and heading date derived from the D genome of natural and resynthetic allohexaploid wheat - Huanwen Xu; Runqi Zhang; Mingming Wang; Linghong Li; Lei Yan; Zhen Wang; Jun Zhu; Xiyong Chen; Aiju Zhao; Zhenqi Su; Jiewen Xing; Qixin Sun; et al. (Theoretical and Applied Genetics, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Seasonality and Sex-Biased Fluctuation of Birth Weight in Tibetan Populations - Yaoxi He; Jun Li; Tian Yue; Wangshan Zheng; Yongbo Guo; Hui Zhang; Li Chen; Chunxia Li; Hongyan Li; Chaoying Cui; Ouzhuluobu; Xuebin Qi; et al. (Phenomics, 2022)

Genetic dissection of quantitative trait loci for grain size and weight by high-resolution genetic mapping in bread wheat (Triticum aestivum L.) - Tao Li; Guangbing Deng; Yan Su; Zhao Yang; Yanyan Tang; Jinhui Wang; Juanyu Zhang; Xvebing Qiu; Xi Pu; Wuyun Yang; Jun Li; Zehou Liu; et al. (Theoretical and Applied Genetics, 2022)

Seasonal and spatial variations in the phytoplankton community and their correlation with environmental factors in the Jinjiang River Estuary in Quanzhou, China - Yanmei Wu; Peiyong Guo; Haitao Su; Yuxuan Zhang; Jun Deng; Meixian Wang; Yinshi Sun; Yanqi Li; Xiaoyan Zhang (Environmental Monitoring and Assessment, 2022)

Characterization of the novel hybrid cultivar E25 of Saccharina japonica in the northern farming region of China - Li Su; Ti Feng Shan; Jing Li; Su Qin Gao; Shao Jun Pang; Xiao Fei Leng; Yan Zhang; Ming Fu Zhang; Hong Tao Gao (Journal of Applied Phycology, 2021)

Susceptibility assessment of small, shallow and clustered landslide - Xuemei Liu; Pengcheng Su; Yong Li; Jun Zhang; Taiqiang Yang (Earth Science Informatics, 2021)

Identification and validation of two major QTLs for spike compactness and length in bread wheat (Triticum aestivum L.) showing pleiotropic effects on yield-related traits - Tao Li; Guangbing Deng; Yan Su; Zhao Yang; Yanyan Tang; Jinhui Wang; Xvebing Qiu; Xi Pu; Jun Li; Zehou Liu; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

Comparison of the Bulk and Rhizosphere Soil Prokaryotic Communities Between Wild and Reintroduced Manglietiastrum sinicum Plants, a Threatened Species with Extremely Small Populations - Dai-Fa Su; Qing-Qing Shen; Jun-Yu Yang; Zhi-Ying Li; Wei Xiao; Yong-Xia Wang; Zhang-Gui Ding; Xiao-Long Cui (Current Microbiology, 2021)

An novel energy dissipator with self-recovery capability after deformation for structurally energy-dissipating rock-shed - Qi-jun Xie; Li-jun Su; Hao Bai; Hao Tang; Chong-lei Zhang; Fang-wei Yu (Journal of Mountain Science, 2021)

Influence of grain segregation on the behavior of sand in triaxial tests - Fang-wei Yu; Xiong-zhi Peng; Li-jun Su (Journal of Mountain Science, 2021)

Supply‐controlled calcium carbonate dissolution decouples the seasonal dissolved oxygen and pH minima in Chesapeake Bay - Jianzhong Su; Wei‐Jun Cai; Jeremy M. Testa; Jean R. Brodeur; Baoshan Chen; K. Michael Scaboo; Ming Li; Chunqi Shen; Margaret Dolan; Yuan‐Yuan Xu; Yafeng Zhang; Najid Hussain (Limnology and Oceanography, 2021)
Acidification can present a stress on organisms and habitats in estuaries in addition to hypoxia. Although oxygen and pH decreases are generally coupled due to aerobic respiration, pH dynamics may be more complex given the multiple modes of buffering in the carbonate system. We studied the seasonal cycle of dissolved oxygen (DO), pH, dissolved inorganic carbon, total alkalinity, and calcium ion (Ca 2+ ) along the main channel of Chesapeake Bay from May to October in 2016. Contrary to the expected co‐occurrence of seasonal DO and pH declines in subsurface water, we found that the pH decline ended in June while the DO decline continued until August in mid‐Chesapeake Bay. We discovered that aerobic respiration was strong from May to August, but carbonate dissolution was minor in May and June and became substantial in August, which buffered further pH declines and caused the seasonal DO and pH minima mismatch. The rate of calcium carbonate (CaCO 3 ) dissolution was not primarily controlled by the saturation state in bottom water, but was instead likely controlled by the supply of CaCO 3 particles. The seasonal variability of Ca 2+ addition in the mid‐bay was connected to Ca 2+ removal in the upper bay, and the timing of high carbonate dissolution coincided with peak seasonal biomass of upper Bay submerged aquatic vegetation. This study suggests a mechanism for a novel decoupling of DO and pH in estuarine waters associated with CaCO 3 , but future studies are needed to fully investigate the seasonality of physical transport and cycling of CaCO 3 .

Octamer transcription factor-1 induces the Warburg effect via up-regulation of hexokinase 2 in non-small cell lung cancer - Zhen Li; Jin Su; Mingming Sun; Jiaqi Song; Huanran Sun; Jun Fan; Guo Chen; Changliang Shan; Qi Qi; Shuai Zhang (Molecular and Cellular Biochemistry, 2021)

Sporadic hand, foot, and mouth disease cases associated with non-C4 enterovirus 71 strains in Xiamen, China, from 2009 to 2018 - Mengyuan Chen; Shuizhen He; Qiang Yan; Jianmei Zhang; Caiyu Li; Xiaosong Su; Shiyin Zhang; Tingdong Li; Shengxiang Ge; Min Chen; Jun Zhang; Ningshao Xia (Archives of Virology, 2021)

The interaction of MYB, bHLH and WD40 transcription factors in red pear (Pyrus pyrifolia) peel - Daolei Cui; Shuxin Zhao; Huini Xu; Andrew C. Allan; Xiaodong Zhang; Lei Fan; Limei Chen; Jun Su; Quan Shu; Kunzhi Li (Plant Molecular Biology, 2021)

Research on displacement prediction of step-type landslide under the influence of various environmental factors based on intelligent WCA-ELM in the Three Gorges Reservoir area - Yong-gang Zhang; Xin-quan Chen; Rao-ping Liao; Jun-li Wan; Zheng-ying He; Zi-xin Zhao; Yan Zhang; Zheng-yang Su (Natural Hazards, 2021)

Evaluating the Friendliness of Pedestrian Footbridges Using Visibility Analysis: A Case Study in Wuhan - Jun Li; Shuang Wu; Zhiwei Luo; Jingyang Hou; Wenbo Zhang; Xueye Chen; Junru Su; Shen Ying (Journal of Geovisualization and Spatial Analysis, 2021)

Risk assessment of glacial debris flow on alpine highway under climate change: A case study of Aierkuran Gully along Karakoram Highway - Ya-mei Li; Li-jun Su; Qiang Zou; Xue-li Wei (Journal of Mountain Science, 2021)

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

KCNQ Channels in the Mesolimbic Reward Circuit Regulate Nociception in Chronic Pain in Mice - Hao-Ran Wang; Su-Wan Hu; Song Zhang; Yu Song; Xiao-Yi Wang; Lei Wang; Yang-Yang Li; Yu-Mei Yu; He Liu; Di Liu; Hai-Lei Ding; Jun-Li Cao (Neuroscience Bulletin, 2021)
Mesocorticolimbic dopaminergic (DA) neurons have been implicated in regulating nociception in chronic pain, yet the mechanisms are barely understood. Here, we found that chronic constructive injury (CCI) in mice increased the firing activity and decreased the KCNQ channel-mediated M-currents in ventral tegmental area (VTA) DA neurons projecting to the nucleus accumbens (NAc). Chemogenetic inhibition of the VTA-to-NAc DA neurons alleviated CCI-induced thermal nociception. Opposite changes in the firing activity and M-currents were recorded in VTA DA neurons projecting to the medial prefrontal cortex (mPFC) but did not affect nociception. In addition, intra-VTA injection of retigabine, a KCNQ opener, while reversing the changes of the VTA-to-NAc DA neurons, alleviated CCI-induced nociception, and this was abolished by injecting exogenous BDNF into the NAc. Taken together, these findings highlight a vital role of KCNQ channel-mediated modulation of mesolimbic DA activity in regulating thermal nociception in the chronic pain state.

Bjerkandera adusta M1 inhibits the growth of Fusarium oxysporum f. sp. conglutinans and fusarium wilt incidence in Brassica napus L. - Xiao Feng; Su-Ping Li; Yi-Fan Lu; Jing-Jie Zhang; Yun-Yun Zhu; Yong Li; Hong-Jun Yang; Xin-Hua He (Journal of Plant Pathology, 2021)

Experimental validation of a new semi-empirical impact force model of the dry granular flow impact against a rigid barrier - Yuan-Jun Jiang; Xiao-Yi Fan; Li-Jun Su; Si-you Xiao; Jing Sui; Rui-Xiao Zhang; Yue Song; Zhi-Wen Shen (Landslides, 2021)

Correction to: Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Bai; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Ba; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Impacts of native vegetation on the hydraulic properties of the concentrated flows in bank gullies - Zheng-an Su; Zhou-yao He; Tao Zhou; Jun-jie Wang; Xiao-yi Wang; Li-juan Wang; Hai-dong Fang; Liang-tao Shi; Yi-han Liu; Zuo Wu (Journal of Mountain Science, 2021)

Effects of simulated drought stress on carotenoid contents and expression of related genes in carrot taproots - Rong-Rong Zhang; Ya-Hui Wang; Tong Li; Guo-Fei Tan; Jian-Ping Tao; Xiao-Jun Su; Zhi-Sheng Xu; Yong-Sheng Tian; Ai-Sheng Xiong (Protoplasma, 2021)

Transformation of coccolithophorid Emiliania huxleyi harboring a marine virus (Coccolithoviruses) serine palmitoyltransferase (SPT) gene by electroporation - Weicong Cai; Xueting Wang; Jinjing Su; Jian Li; Jun Zeng; Guiling Li; Jingwen Liu (Journal of Oceanology and Limnology, 2021)

Pullout Behavior of Sensor-Enabled Geobelts in Weathered Rock Material–Granulated Rubber Mixtures - Yi-lin Wang; Xin-zhuang Cui; Jin Li; Lei Wang; Jun Li; Jun-wei Su (Geotechnical and Geological Engineering, 2021)

Erratum to: Landslide susceptibility assessment at Kathmandu Kyirong Highway Corridor in pre-quake, co-seismic and post-quake situations - Susmita Dhakal; Peng Cui; Li-jun Su; Olga Mavrouli; Qiang Zou; Jian-qiang Zhang; Lalu Paudel; Nirusha Shrestha (Journal of Mountain Science, 2020)

Dietary lipid concentrations influence growth, body composition, morphology of the liver and mid-intestine, and antioxidant status of marbled eel (Anguilla marmorata) - Shi-Jun Chen; Peng Liu; You-Ming Jia; Hong-Ping Liao; Shao-Xuan Zhu; Li-Liu Zhou; Xue-Ming Dan; Li Liu; Jia-Hao Li; Su-Bi Zheng; Jun-Jiang Yang; Lian Gan (Aquaculture International, 2020)

Landslide susceptibility assessment at Kathmandu Kyirong Highway Corridor in pre-quake, co-seismic and post-quake situations - Susmita Dhakal; Peng Cui; Li-jun Su; Olga Mavrouli; Qiang Zou; Jian-qiang Zhang; Lalu Paudel; Nirusha Shrestha (Journal of Mountain Science, 2020)

Experimental and theoretical study of mechanical properties of root-soil interface for slope protection - Li-jun Su; Bing-li Hu; Qi-jun Xie; Fang-wei Yu; Chong-lei Zhang (Journal of Mountain Science, 2020)

Directional seismic response to the complex topography: A case study of 2013 Lushan Ms 7.0 earthquake - Bo Zhao; Yun-sheng Wang; Li-jun Su; Yong-hong Luo; Jing Zhang (Journal of Mountain Science, 2020)

TMEM88 modulates the secretion of inflammatory factors by regulating YAP signaling pathway in alcoholic liver disease - Liang-yun Li; Chen-chen Yang; Su-wen Li; Yu-min Liu; Hao-dong Li; Shuang Hu; Hong Zhou; Jin-liang Wang; Hang Shen; Xiao-ming Meng; Jun Li; Tao Xu (Inflammation Research, 2020)

Landslide characteristics and its impact on tourism for two roadside towns along the Kathmandu Kyirong Highway - Susmita Dhakal; Peng Cui; Chandra Prasad Rijal; Li-jun Su; Qiang Zou; Olga Mavrouli; Chun-hao Wu (Journal of Mountain Science, 2020)

Source partitioning of oxygen‐consuming organic matter in the hypoxic zone of the Chesapeake Bay - Jianzhong Su; Wei‐Jun Cai; Jean Brodeur; Najid Hussain; Baoshan Chen; Jeremy M. Testa; K. Michael Scaboo; Deb P. Jaisi; Qiang Li; Minhan Dai; Jeffrey Cornwell (Limnology and Oceanography, 2020)
We surveyed the carbonate system along the main channel of the Chesapeake Bay in June 2016 to elucidate carbonate dynamics and the associated sources of oxygen‐consuming organic matter. Using a two endmember mixing calculation, chemical proxies, and stoichiometry, we demonstrated that in early summer, dissolved inorganic carbon (DIC) dynamics were controlled by aerobic respiration in the water column (43%), sulfate reduction in the sediment (39%), atmospheric CO 2 invasion (13%), and CaCO 3 dissolution (5%). A mass balance of the DIC concentration and its stable isotope suggested that the apparent δ 13 C of oxygen‐consuming organic matter was −19.4 ± 0.3‰. The bulk composition of particulate organic matter also reflected a dominance of algal material (C/N = ~ 6, δ 13 C > −25‰). Therefore, we concluded that the decomposition of autochthonous organic matter (i.e., eutrophication‐stimulated primary production) was the dominant process consuming oxygen, while allochthonous organic matter (terrestrially derived) made minor contributions to oxygen consumption in the hypoxic zone in June 2016. These findings in the Chesapeake Bay contrast with another hypoxic estuarine ecosystem, the Pearl River Estuary in China where allochthonous organic matter contributed significantly to oxygen consumption. The differences between these two systems in terms of hydrology, quantity and quality of organic matter, and physical characteristics are discussed to yield new insights on the formation and maintenance of hypoxia. In both systems, autochthonous organic matter dominates oxygen depletion, indicating that nutrient management and reduction are useful actions to control and mitigate the occurrence of hypoxia for the restoration of ecosystem.

The bHLH gene family and its response to saline stress in Jilin ginseng, Panax ginseng C.A. Meyer - Lei Zhu; Mingzhu Zhao; Mengyao Chen; Li Li; Yue Jiang; Sizhang Liu; Yang Jiang; Kangyu Wang; Yanfang Wang; Chunyu Sun; Jing Chen; Ping Chen; et al. (Molecular Genetics and Genomics, 2020)

Landslide susceptibility analysis of Karakoram highway using analytical hierarchy process and scoops 3D - Barira Rashid; Javed Iqbal; Li-jun Su (Journal of Mountain Science, 2020)

Immunomagnetic separation-based nanogold enhanced surface plasmon resonance and colloidal gold test strips for rapid detection of Vibrio parahaemolyticus - Jun Zhou; Chundan Zhang; Xuan Zhang; Chenyang Lu; Tinghong Ming; Ye Li; Xiurong Su (Archives of Microbiology, 2020)

Formation of highly graphitic char derived from phenolic resin carbonization by Ni-Zn-B alloy - Qiangqiang Ren; Limo He; Song Hu; Hanjian Li; Shanxue Li; Zengtong Deng; Gongxiang Song; Sheng Su; Yi Wang; Jun Xiang (Environmental Science and Pollution Research, 2020)

The association between prenatal endocrine-disrupting chemical exposure and altered resting-state brain fMRI in teenagers - Jun-Cheng Weng; Chi Ieong Hong; Jeng-Dau Tasi; Chao-Yu Shen; Pen-Hua Su; Shu-Li Wang (Brain Structure and Function, 2020)

Estimation of hydraulic parameters of an unconfined aquifer by using geoelectrical and pumping test data: a case study of the Mandi Bahauddin District, Pakistan - Faheem Ullah; Li-Jun Su; Hafeez Ullah; Aamir Asghar (Arabian Journal of Geosciences, 2020)

A DTW distance-based seismic waveform clustering method for layers of varying thickness - Zhong Hong; Kun-Hong Li; Ming-Jun Su; Guang-Min Hu; Jun Yang; Gai Gao; Bin Hao (Applied Geophysics, 2020)

Method for obtaining high-resolution velocity spectrum based on weighted similarity - Xing-Rong Xu; Qin Su; Jun-Fa Xie; Jing Wang; Long-Jiang Kou; Meng-Li Liu (Applied Geophysics, 2020)

Identification of gas-bearing reservoirs based on the simultaneous inversion of NMR dual-TW logging data - Jianwei Li; Youlong Zou; Jun Li; Heping Pan; Song Hu; Junlei Su; Lei Wang; Jun Liu; Yue Guo (Acta Geophysica, 2020)

NK cell reconstitution following unmanipulated HLA-mismatched/haploidentical transplantation compared with matched sibling transplantation - Li-Juan Hu; Xun-Hong Cao; Xing-Xing Yu; Xue-Fei Liu; Xiao-Su Zhao; Ying-Jun Chang; Xiao-Hui Zhang; Lan-Ping Xu; Yu Wang; Kai-Yan Liu; Xiao-Jun Huang; Xiang-Yu Zhao (Science China Life Sciences, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Genetic diversity of strawberry mild yellow edge virus from eastern Canada - Yu Xiang; Xianzhou Nie; Mike Bernardy; Jun-jun Liu; Li Su; Basdeo Bhagwat; Virginia Dickison; Janesse Holmes; Jenna M. Grose; Alexa C. Creelman (Archives of Virology, 2020)

NMR-based metabolomics reveals the metabolite profiles of Vibrio parahaemolyticus under blood agar stimulation - Jun Zhou; Chundan Zhang; Jiaojiao Han; Chenyang Lu; Ye Li; Tinghong Ming; Xiurong Su (Archives of Microbiology, 2020)

Identification and validation of the superior alleles for wheat kernel traits detected by genome-wide association study under different nitrogen environments - Na Zhang; Xilan Zhang; Liqiang Song; Qiannan Su; Shuai Zhang; Jiajia Liu; Wei Zhang; Xiaoyi Fu; Minghui Zhao; Lijing Sun; Jun Ji; Wenchen Qiao; et al. (Euphytica, 2020)

cDNA-AFLP analysis of differentially expressed genes during microspore embryogenesis in non-heading Chinese cabbage - Ya Zhang; Su-yan Gao; Huan-huan Liu; Xi-lin Zhang; Ai-song Zeng; Jian-jun Wang; Xi-lin Hou; Ying Li (In Vitro Cellular & Developmental Biology - Plant, 2020)

A Coupled Model for Heat and Moisture Transport Simulation in Porous Materials Exposed to Thermal Radiation - Yun Su; Jun Li; Xianghui Zhang (Transport in Porous Media, 2020)

Collagen-binding basic fibroblast growth factor improves functional remodeling of scarred endometrium in uterine infertile women: a pilot study - Peipei Jiang; Xiaoqiu Tang; Huiyan Wang; Chenyan Dai; Jing Su; Hui Zhu; Minmin Song; Jingyu Liu; Ziqing Nan; Tong Ru; Yaling Li; Jingmei Wang; et al. (Science China Life Sciences, 2019)

Root diversity in sesame (Sesamum indicum L.): insights into the morphological, anatomical and gene expression profiles - Ruqi Su; Rong Zhou; Marie Ali Mmadi; Donghua Li; Lu Qin; Aili Liu; Jianqiang Wang; Yuan Gao; Mengyuan Wei; Lisong Shi; Ziming Wu; Jun You; et al. (Planta, 2019)

Estimating the maximum impact force of dry granular flow based on pileup characteristics - Si-you Xiao; Li-jun Su; Yuan-jun Jiang; Alam Mehtab; Cheng Li; Dao-chuan Liu (Journal of Mountain Science, 2019)

Antihyperlipidemic glycosides from the root bark of Lycium chinense - Hui Chen; Yu-Jie Li; Yan-Jun Sun; Xiao-Kun Li; Gong Jian-Hong; Ya Wu; Fang-Yi Su; Kun Du; Yan-Li Zhang; Wei-Sheng Feng (Natural Product Research, 2019)

Comparison of two noninvasive methods for measuring the pigment content in foliose macrolichens - Shuai Liu; Su Li; Xiao-Yang Fan; Guo-Di Yuan; Tao Hu; Xian-Meng Shi; Jun-Biao Huang; Xiao-Yan Pu; Chuan-Sheng Wu (Photosynthesis Research, 2019)

Numerical analysis of hard rock blasting unloading effects in high in situ stress fields - Si-You Xiao; Li-Jun Su; Yuan-Jun Jiang; Zhi-Xiang Liu (Bulletin of Engineering Geology and the Environment, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Molecular diversity and biogeography of benthic ciliates in the Bohai Sea and Yellow Sea - Guihao Li; Lei Su; Qianqian Zhang; Xiaoli Zhang; Jun Gong (Acta Oceanologica Sinica, 2019)

Virulence regulation of cel‐ EIIB protein mediated PTS system in Streptococcus agalactiae in Nile tilapia - Jun Xu; Yun‐Dan Xie; Ling Liu; Song Guo; You‐Lu Su; An‐Xing Li (Journal of Fish Diseases, 2019)
Streptococcus agalactiae is a major pathogen of tilapia causing significant economic losses for the global aquatic industry yearly. To elucidate the role of cel‐ EIIB protein‐mediated phosphotransferase systems ( PTS ) in the virulence regulation of S. agalactiae , cel‐ EIIB gene deletion in a virulent strain THN 0901 was achieved by homologous recombination. The cellobiose utilization of △ cel‐ EIIB strain was significantly decreased relative to S.a . THN 0901 strain incubating in LB with 10 mg/ ml cellobiose ( p cel‐ EIIB strain was also significantly decreased when cultured in BHI medium ( p cel‐ EIIB strain was dramatically decreased (20%), of which S.a . THN 0901 strain and △ cel‐ EIIB ::i strain were 53.33% and 50%, respectively. The competition experience using tilapia model indicated the invasion and colonization ability of △ cel‐ EIIB strain was significantly weaker than that of S.a . THN 0901 strain ( p cel‐ EIIB ::i strain, the mRNA expression of csrS , csrR , rgfA, rgfC, bgrR and bgrS was significantly downregulated in △ cel‐ EIIB strain ( p EIIB protein‐mediated cel‐ PTS not only contributes to biofilm formation and virulence regulation, but also plays an important role in the invasion and colonization of S. agalactiae .

Rutile in HP Rocks from the Western Tianshan, China: Mineralogy and Its Economic Implications - Wen Su; Jilei Li; Qian Mao; Jun Gao; Xin Liu; Fei Chen; Xiao-Mei Ge (Journal of Earth Science, 2018)

Rapid estimation of microbial biomass in acid red soils with and without substrate incorporation - Peng Su; Yong Liu; Sifan Wang; Zhongqi Yan; Shan Wang; Lian Zhu; Jun Lou; Fangbai Li (Journal of Soils and Sediments, 2018)

Biological floating bed and bio-contact oxidation processes for landscape water treatment: simultaneous removal of Microcystis aeruginosa, TOC, nitrogen and phosphorus - Jun feng Su; Dong hui Liang; Le Fu; Li Wei; Min Ma (Environmental Science and Pollution Research, 2018)

Dynamic behaviour of weathered red mudstone in Sichuan (China) under triaxial cyclic loading - Chong-lei Zhang; Guan-lu Jiang; Li-jun Su; Wei-ming Liu (Journal of Mountain Science, 2018)

Comparison of instrumental and interpolated meteorological data-based summer temperature reconstructions on Mt. Taibai in the Qinling Mountains, northwestern China - Jin Qin; Hongying Bai; Kai Su; Rongjuan Liu; Danping Zhai; Jun Wang; Shuheng Li; Qi Zhou; Bin Li (Theoretical and Applied Climatology, 2018)

Effect of dry density on the liquefaction behaviour of Quaternary silt - Chong-lei Zhang; Guan-lu Jiang; Li-jun Su; Wei-ming Liu; Gong-dan Zhou (Journal of Mountain Science, 2018)

Anti-inflammatory and anti-angiogenic activities in vitro of eight diterpenes from Daphne genkwa based on hierarchical cluster and principal component analysis - Ling Wang; Xin-Yi Lan; Jun Ji; Chun-Feng Zhang; Fei Li; Chong-Zhi Wang; Chun-Su Yuan (Journal of Natural Medicines, 2018)

Seismic stability analysis of slopes with pre-existing slip surfaces - Li-jun Su; Chang-ning Sun; Fang-wei Yu; Sarfraz Ali (Journal of Mountain Science, 2018)

Development of a reverse transcription recombinase-aided amplification assay for the detection of coxsackievirus A10 and coxsackievirus A6 RNA - Teng-fei Yan; Xin-na Li; Le Wang; Chen Chen; Su-xia Duan; Ju-ju Qi; Li-Xin Li; Xue-jun Ma (Archives of Virology, 2018)

Morphology and multigene phylogeny reveal new genus and species of Torulaceae from freshwater habitats in northwestern Yunnan, China - Xi-Jun Su; Zong-Long Luo; Rajesh Jeewon; Darbhe J. Bhat; Dan-Feng Bao; Wen-Li Li; Yu-E Hao; Hong-Yan Su; Kevin D. Hyde (Mycological Progress, 2018)

Morphological and molecular taxonomy of novel species Pleurotheciaceae from freshwater habitats in Yunnan, China - Zong-Long Luo; Kevin D. Hyde; Darbhe J. Bhat; Rajesh Jeewon; Sajeewa S. N. Maharachchikumbura; Dan-Feng Bao; Wen-Li Li; Xi-Jun Su; Xiao-Yan Yang; Hong-Yan Su (Mycological Progress, 2018)

Molecular characterization of a NADPH–cytochrome P450 reductase gene from the rice leaffolder, Cnaphalocrocis medinalis (Lepidoptera: Pyralidae) - Yu-Xing Zhang; Shi-Guang Li; Xiang-Jun Rao; Su Liu (Applied Entomology and Zoology, 2018)

Ordovician sedimentation and bimodal volcanism in the Southern Qiangtang terrane of northern Tibet: Implications for the evolution of the northern Gondwana margin - Chao-ming Xie; Cai Li; Jian-jun Fan; Li Su (International Geology Review, 2017)

Large-scale hatchery of the kelp Saccharina japonica: a case study experience at Lvshun in northern China - Li Su; Shao Jun Pang; Ti Feng Shan; Xia Li (Journal of Applied Phycology, 2017)

Effect of cement on the stabilization of loess - Chong-lei Zhang; Guan-lu Jiang; Li-jun Su; Gong-dan Zhou (Journal of Mountain Science, 2017)

An Assessment of Genetic Diversity of Yield-Related Traits of Saccharum spontaneum from Yunnan Province, China - Chaohua Xu; Huosheng Su; Hongbo Liu; Xin Lu; Xujuan Li; Chunjia Li; Xiuqin Lin; Jun Mao; Qiuyan Zi; XinLong Liu (Sugar Tech, 2017)

Synthesis and antiproliferative properties of novel naringenin derivatives - Su-You Liu; Jiang Zeng; Kun-Jian Peng; Li-Chao Zhang; Li-Jun Liu; Zhi-Yong Luo; Da-You Ma (Medicinal Chemistry Research, 2017)

Erratum to: Characteristics and triggering mechanism of Xinmo landslide on 24 June 2017 in Sichuan, China - Li-jun Su; Kai-heng Hu; Wei-feng Zhang; Jiao Wang; Yu Lei; Chong-lei Zhang; Peng Cui; Alessandro Pasuto; Quan-hong Zheng (Journal of Mountain Science, 2017)

Oxidative stress promotes myocardial fibrosis by upregulating KCa3.1 channel expression in AGT-REN double transgenic hypertensive mice - Li-Ping Wang; Su-Jing Fan; Shu-Min Li; Xiao-Jun Wang; Jun-Ling Gao; Xiu-Hong Yang (Pflügers Archiv - European Journal of Physiology, 2017)

Neuroprotection of dexmedetomidine against propofol-induced neuroapoptosis partly mediated by PI3K/Akt pathway in hippocampal neurons of fetal rat - Ning Zhang; Quan-ping Su; Wei-xia Zhang; Nian-jun Shi; Hao Zhang; Ling-ping Wang; Zhong-kai Liu; Ke-zhong Li (Journal of Zhejiang University-SCIENCE B, 2017)

Characteristics and triggering mechanism of Xinmo landslide on 24 June 2017 in Sichuan, China - Li-jun Su; Kai-heng Hu; Wei-feng Zhang; Jiao Wang; Yu Lei; Chong-lei Zhang; Peng Cui; Alessandro Pasuto; Quan-hong Zheng (Journal of Mountain Science, 2017)

A back-propagation neural-network-based displacement back analysis for the identification of the geomechanical parameters of the Yonglang landslide in China - Fang-wei Yu; Xiong-zhi Peng; Li-jun Su (Journal of Mountain Science, 2017)

Construction and characterization of a bacterial artificial chromosome library for Camellia sinensis - Yuling Tai; Hao Wang; Chaoling Wei; Ling Su; Min Li; Liqun Wang; Zhaozhao Dai; Lingyun Shao; Jiayue Jiang; Meizhong Luo; Hua Yang; Weiwei Deng; et al. (Tree Genetics & Genomes, 2017)

Novel adefovir mono L-amino acid ester, mono bile acid ester derivatives: Design, synthesis, biological evaluation, and molecular docking study - Ya Chen; Wen Zheng Zhang; Jing Li; Tao Xiao; Jiang Xia Liu; Min Luo; Hang Su; Xiao-Zhong Fu; Ting Liu; Yong-Xi Dong; Yong-Long Zhao; Bin He; et al. (Medicinal Chemistry Research, 2017)

Reduced weed seed shattering by silencing a cultivated rice gene: strategic mitigation for escaped transgenes - Huanxin Yan; Lei Li; Ping Liu; Xiaoqi Jiang; Lei Wang; Jia Fang; Zhimin Lin; Feng Wang; Jun Su; Bao-Rong Lu (Transgenic Research, 2017)

Enhancement of simultaneous algicidal and denitrification of immobilized Acinetobacter sp. J25 with magnetic Fe3O4 nanoparticles - Jun feng Su; Dong hui Liang; Ting lin Huang; Li Wei; Min Ma; Jinsuo Lu (Environmental Science and Pollution Research, 2017)

Analysis on shear wave velocity structure of a gravel landslide based on dual-source surface wave method - Xing-qian Xu; Li-jun Su; Guang-da Zhang; Hong-hu Zhu (Landslides, 2017)

Erratum to: Construction of a thermo-sensitive pRI857 vector for efficient DNA capturing in Escherichia coli - Yang Wang; Kai Zhang; Huijuan Su; Muhan Yang; Jing Ge; Guiyao Li; Jun Yi (Biotechnology Letters, 2017)

Construction of a thermo-sensitive pRI857 vector for efficient DNA capturing in Escherichia coli - Kai Zhang; Huijuan Su; Muhan Yang; Jing Ge; Guiyao Li; Jun Yi; Yang Wang (Biotechnology Letters, 2017)

Similar behavior, different mechanisms: the research of the style bending of Alpinia species - Zhi-Long Su; Xian-Liang Cui; Li Li; Qing-Jun Li; Yin-Ling Luo (Acta Physiologiae Plantarum, 2017)

The Role of Dynamic Contrast-Enhanced MR in Evaluating Level III Collateral Circulation in a Rat Model of Acute Ischemic Stroke - Hui Chen; Nan Liu; Ying Li; Bing Wu; Zihua Su; Guangming Zhu; Jun Hu (Molecular Neurobiology, 2017)

CT Permeability Imaging Predicts Clinical Outcomes in Acute Ischemic Stroke Patients Treated with Intra-arterial Thrombolytic Therapy - Nan Liu; Hui Chen; Bing Wu; Ying Li; Max Wintermark; Alan Jackson; Jun Hu; Yongwei Zhang; Zihua Su; Guangming Zhu; Weiwei Zhang (Molecular Neurobiology, 2017)

A Novel Wheat Nicotianamine Synthase Gene, TaNAS-D, Confers High Salt Tolerance in Transgenic Arabidopsis - Jie Han; Wei Zhang; Lijing Sun; Qiannan Su; Zijing Li; Xiaoli Fan; Na Zhang; Ruiqing Pan; Fa Cui; Jun Ji; Hui Li; Junming Li (Plant Molecular Biology Reporter, 2017)

Impact of weather factors on hand, foot and mouth disease, and its role in short-term incidence trend forecast in Huainan City, Anhui Province - Desheng Zhao; Lulu Wang; Jian Cheng; Jun Xu; Zhiwei Xu; Mingyu Xie; Huihui Yang; Kesheng Li; Lingying Wen; Xu Wang; Heng Zhang; Shusi Wang; et al. (International Journal of Biometeorology, 2017)

Low-Dose Ethanol Preconditioning Protects Against Oxygen-Glucose Deprivation/Reoxygenation-Induced Neuronal Injury By Activating Large Conductance, Ca2+-Activated K+ Channels In Vitro - Fang Su; An-Chen Guo; Wei-Wei Li; Yi-Long Zhao; Zheng-Yi Qu; Yong-Jun Wang; Qun Wang; Yu-Lan Zhu (Neuroscience Bulletin, 2017)

Simultaneous nitrification and denitrification in a novel membrane bioelectrochemical reactor with low membrane fouling tendency - Hui Li; Wei Zuo; Yu Tian; Jun Zhang; Shijing Di; Lipin Li; Xinying Su (Environmental Science and Pollution Research, 2017)

Gastroprotective effect of palmatine against acetic acid-induced gastric ulcers in rats - Ling Wang; Xue Wang; Su-Li Zhang; Xiao-Ming Zhu; Yan-Qi Liu; Zi-Jing Song; Wen-Juan Du; Jun Ji; Cheng-Long Cui; Xin He; Chun-Feng Zhang; Chang-Run Guo; et al. (Journal of Natural Medicines, 2017)

Integrin β8 Deletion Enhances Vascular Dysplasia and Hemorrhage in the Brain of Adult Alk1 Heterozygous Mice - Li Ma; Fanxia Shen; Kristine Jun; Chen Bao; Robert Kuo; William L. Young; Stephen L. Nishimura; Hua Su (Translational Stroke Research, 2016)

Biodegradation of Endosulfan by Bacterial Strain Alcaligenes faecalis JBW4 in Argi-Udic Ferrosols and Hapli-Udic Isohumosols - Yu Zhang; Lusheng Zhu; Jinhua Wang; Jun Wang; Benying Su; Cheng Zhang; Yuting Shao; Chao Li (Water, Air, & Soil Pollution, 2016)

Protective role of ACE2-Ang-(1–7)-Mas in myocardial fibrosis by downregulating KCa3.1 channel via ERK1/2 pathway - Li-Ping Wang; Su-Jing Fan; Shu-Min Li; Xiao-Jun Wang; Jun-Ling Gao; Xiu-Hong Yang (Pflügers Archiv - European Journal of Physiology, 2016)

Landslide susceptibility assessment of the region affected by the 25 April 2015 Gorkha earthquake of Nepal - Amar Deep Regmi; Megh Raj Dhital; Jian-qiang Zhang; Li-jun Su; Xiao-qing Chen (Journal of Mountain Science, 2016)

Ethanol Increases Mechanical Pain Sensitivity in Rats via Activation of GABAA Receptors in Medial Prefrontal Cortex - Kai-Wen Geng; Ting He; Rui-Rui Wang; Chun-Li Li; Wen-Jun Luo; Fang-Fang Wu; Yan Wang; Zhen Li; Yun-Fei Lu; Su-Min Guan; Jun Chen (Neuroscience Bulletin, 2016)

Permeability of novel 4′-N-substituted (aminomethyl) benzoate-7-substituted nicotinic acid ester derivatives of scutellarein in Caco-2 cells and in an in vitro model of the blood-brain barrier - Yu Ou; Min Luo; Yong-Xi Dong; Hang Su; Xiao-Zhong Fu; Yu-Feng Cha; Shun Zhang; Yong-Long Zhao; Yong-Jun Li; Yong-Lin Wang (Medicinal Chemistry Research, 2016)

The spatial distribution characteristics of shallow fissures of a landslide in the Wenchuan earthquake area - Xing-qian Xu; Li-jun Su; Chao Liu (Journal of Mountain Science, 2016)

CGRP 8-37 enhances lipopolysaccharide-induced acute lung injury and regulating aquaporin 1 and 5 expressions in rats - Fu Hong-min; Huangfu Chun-rong; Zheng Rui; Su Li-na; Wang Ya-jun; Li Li (Journal of Physiology and Biochemistry, 2016)

Breeding of an elite cultivar Haibao No. 1 of Undaria pinnatifida (Phaeophyceae) through gametophyte clone crossing and consecutive selection - Ti Feng Shan; Shao Jun Pang; Jing Li; Su Qin Gao (Journal of Applied Phycology, 2016)

Particle breakage and the mobilized drained shear strengths of sand - Fang-wei Yu; Li-jun Su (Journal of Mountain Science, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

Salusin β Within the Nucleus Tractus Solitarii Suppresses Blood Pressure Via Inhibiting the Activities of Presympathetic Neurons in the Rostral Ventrolateral Medulla in Spontaneously Hypertensive Rats - Hong-Bao Li; Yan Lu; Jin-Jun Liu; Yu-Wang Miao; Tian-Zhen Zheng; Qing Su; Jie Qi; Hong Tan; Zu-Yi Yuan; Guo-Qing Zhu; Yu-Ming Kang (Cardiovascular Toxicology, 2016)

Human amniotic epithelial stem cells promote wound healing by facilitating migration and proliferation of keratinocytes via ERK, JNK and AKT signaling pathways - Bin Zhao; Jia-Qi Liu; Zhao Zheng; Jun Zhang; Shu-Yue Wang; Shi-Chao Han; Qin Zhou; Hao Guan; Chao Li; Lin-Lin Su; Da-Hai Hu (Cell and Tissue Research, 2016)

Downregulation of Glutamate Transporter EAAT4 by Conditional Knockout of Rheb1 in Cerebellar Purkinje Cells - Nan-Wei Jiang; De-Juan Wang; Ya-Jun Xie; Liang Zhou; Li-Da Su; Huashun Li; Qin-Wen Wang; Ying Shen (The Cerebellum, 2016)

Purification, Chemical Characterization, and Bioactivity of an Extracellular Polysaccharide Produced by the Marine Sponge Endogenous Fungus Alternaria sp. SP-32 - Yin Chen; Wen-Jun Mao; Meng-Xia Yan; Xue Liu; Shu-Yao Wang; Zheng Xia; Bo Xiao; Su-Jian Cao; Bao-Qin Yang; Jie Li (Marine Biotechnology, 2016)

Engrailed-2 might play an anti-oncogenic role in clear-cell renal cell carcinoma - Cai-yong Lai; Yin Xu; Gan-shen Yu; Xun Wu; Yun-fei Li; Bin Pan; Bao-li Heng; Yi-jun Xue; Ze-xuan Su (Journal of Molecular Histology, 2016)

The Oldest Cranium of Sinomastodon (Proboscidea, Gomphotheriidae), Discovered in the Uppermost Miocene of Southwestern China: Implications for the Origin and Migration of This Taxon - Shi-Qi Wang; Xue-Ping Ji; Nina G. Jablonski; Denise F. Su; Jun-Yi Ge; Chang-Fen Ding; Teng-Song Yu; Wen-Qi Li; Jaroon Duangkrayom (Journal of Mammalian Evolution, 2016)

Geo-engineered buffer capacity of two-layered absorbing system under the impact of rock avalanches based on Discrete Element Method - Yu-zhang Bi; Si-ming He; Xin-po Li; Yong Wu; Qiang Xu; Chao-jun Ouyang; Li-Jun Su; Hao Wang (Journal of Mountain Science, 2016)

The impacts of migrant workers consumption on energy use and CO2 emissions in China - Jing-Li Fan; Hua Liao; Bao-Jun Tang; Su-Yan Pan; Hao Yu; Yi-Ming Wei (Natural Hazards, 2016)

Urinary trypsin inhibitor attenuates LPS-induced endothelial barrier dysfunction by upregulation of vascular endothelial-cadherin expression - Jie Chen; Jun Wang; Chenglei Su; Wenyi Qian; Li Sun; Hao Sun; Junjie Chen; Huazhong Zhang; Jinsong Zhang (Inflammation Research, 2016)

Intraspecific crossing of Saccharina japonica using distantly related unialgal gametophytes benefits kelp farming by improving blade quality and productivity at Sanggou Bay, China - Xiao Bo Zhao; Shao Jun Pang; Feng Liu; Ti Feng Shan; Jing Li; Su Qin Gao; Hyung Geun Kim (Journal of Applied Phycology, 2016)

AcSKP1, a multiplex PCR-based co-dominant marker in complete linkage disequilibrium with the male-fertility restoration (Ms) locus, and its application in open-pollinated populations of onion - Yu Meng Huo; Bing Jiang Liu; Yan Yan Yang; Jun Miao; Li Min Gao; Su Ping Kong; Zhen Bao Wang; Hidemi Kitano; Xiong Wu (Euphytica, 2015)

Population genetic structure and approximate B ayesian computation analyses reveal the southern origin and northward dispersal of the oriental fruit moth G rapholita molesta ( L epidoptera: T ortricidae) in its native range - Shu‐Jun Wei; Li‐Jun Cao; Ya‐Jun Gong; Bao‐Cai Shi; Su Wang; Fan Zhang; Xiao‐Jun Guo; Yuan‐Min Wang; Xue‐Xin Chen (Molecular Ecology, 2015)
The oriental fruit moth ( OFM ) Grapholita molesta is one of the most destructive orchard pests. Assumed to be native to China, the moth is now distributed throughout the world. However, the evolutionary history of this moth in its native range remains unknown. In this study, we explored the population genetic structure, dispersal routes and demographic history of the OFM in China and South Korea based on mitochondrial genes and microsatellite loci. The Mantel test indicated a significant correlation between genetic distance and geographical distance in the populations. Bayesian analysis of population genetic structure ( baps ) identified four nested clusters, while the geneland analysis inferred five genetic groups with spatial discontinuities. Based on the approximate Bayesian computation approach, we found that the OFM was originated from southern China near the Shilin area of Yunnan Province. The early divergence and dispersal of this moth was dated to the Penultimate glaciation of Pleistocene. Further dispersal from southern to northern region of China occurred before the last glacial maximum, while the expansion of population size in the derived populations in northern region of China occurred after the last glacial maximum. Our results indicated that the current distribution and structure of the OFM were complicatedly influenced by climatic and geological events and human activities of cultivation and wide dissemination of peach in ancient China. We provide an example on revealing the origin and dispersal history of an agricultural pest insect in its native range as well as the underlying factors.

Transdifferentiation of bone marrow-derived mesenchymal stem cells into salivary gland-like cells using a novel culture method - Liang Liang; Jun Wang; Yuming Zhang; Zhiyuan Shen; Jun Zheng; Jianhu Li; Zhongping Su; Juan Cai; Wei Jiang; Moyi Sun (Biotechnology Letters, 2015)

Characterization of 26 deletion CNVs reveals the frequent occurrence of micro-mutations within the breakpoint-flanking regions and frequent repair of double-strand breaks by templated insertions derived from remote genomic regions - Ye Wang; Peiqiang Su; Bin Hu; Wenjuan Zhu; Qibin Li; Ping Yuan; Jiangchao Li; Xinyuan Guan; Fucheng Li; Xiangyi Jing; Ru Li; Yongling Zhang; et al. (Human Genetics, 2015)

Phytoplankton Dynamics and Its Further Implication for Particulate Organic Carbon in Surface Waters of a Tropical/Subtropical Estuary - Zhuo-Yi Zhu; Su-Mei Liu; Ying Wu; Ying Li; Jing Zhang; Jun Hu (Estuaries and Coasts, 2015)

Identification and localized expression of putative K+/H+ antiporter genes in Arabidopsis - Lei Han; Jun Lin Li; Li Wang; Wei Ming Shi; Yan Hua Su (Acta Physiologiae Plantarum, 2015)

In vivo expression patterns of microRNAs of Gallid herpesvirus 2 (GaHV-2) during the virus life cycle and development of Marek’s disease lymphomas - Pu Zhao; Xiu-Jie Li; Man Teng; Lu Dang; Zu-Hua Yu; Jia-Qi Chi; Jing-Wei Su; Gai-Ping Zhang; Jun Luo (Virus Genes, 2015)

Paenibacillus wulumuqiensis sp. nov. and Paenibacillus dauci sp. nov., two novel species of the genus Paenibacillus - Jing Zhu; Wei Wang; Shan-Hui Li; Su-Qin Song; Yu-Qing Xie; Qi-Yong Tang; Ghenijan Osman; Yu-Hu Shi; Zhi-Dong Zhang; Wen-Jun Li (Archives of Microbiology, 2015)

MicroRNA expression profiling of p-phenylenediamine treatment in human keratinocyte cell line - Hwa Jun Cha; Ok-Kyu Lee; Soo Yeon Kim; Jung-Min Ko; Su Young Kim; Ji Hye Son; Hyun Joo Han; Shunhua Li; Soo Young Kim; Kyu Joong Ahn; In-Sook An; Sungkwan An; et al. (Molecular & Cellular Toxicology, 2015)

LGI1 is Involved in the Development of Mouse Brain - Li-Da Su; Ya-Jun Xie; Liang Zhou; Ying Shen; Ying-Hong Hu (The Cerebellum, 2015)

Expression Analysis of Two P450 Monooxygenase Genes of the Tobacco Cutworm Moth (Spodoptera litura) at Different Developmental Stages and in Response to Plant Allelochemicals - Rui-Long Wang; Jun Li; Christian Staehelin; Xiao-Wei Xin; Yi-Juan Su; Ren-Sen Zeng (Journal of Chemical Ecology, 2015)

Occurrence assessment of earth fissure based on genetic algorithms and artificial neural networks in Su-Xi-Chang land subsidence area, China - Wenjing Zhang; Li Gao; Xun Jiao; Jun Yu; Xiaosi Su; Shanghai Du (Geosciences Journal, 2014)

Role of SIRT1 in Streptococcus pneumoniae-induced human β-defensin-2 and interleukin-8 expression in A549 cell - Li Lin; Shun-hang Wen; Shu-zhen Guo; Xiao-yan Su; Hu-jun Wu; Lei Chong; Hai-lin Zhang; Wei-xi Zhang; Chang-chong Li (Molecular and Cellular Biochemistry, 2014)

Quantitative trait loci analysis of individual and total isoflavone contents in soybean seeds - HAI JUN ZHANG; JING WEN LI; YA JING LIU; WEN ZHU JIANG; XING LIN DU; LIN LI; XIAO WEI Li; LIAN TAI SU; QING YU WANG; YING WANG (Journal of Genetics, 2014)

Change and Significance of IL-8, IL-4, and IL-10 in the Pathogenesis of Terminal Ileitis in SD Rat - Hong-yu Zhou; Jun Yan; Li Fang; Hui Zhang; Li-guo Su; Guo-hua Zhou (Cell Biochemistry and Biophysics, 2014)

Silencing heat shock protein 27 (HSP27) inhibits the proliferation and migration of vascular smooth muscle cells in vitro - Jie Huang; Liang-di Xie; Li Luo; Su-li Zheng; Hua-jun Wang; Chang-sheng Xu (Molecular and Cellular Biochemistry, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Regulation of synchronism by abscisic-acid-responsive small noncoding RNAs during somatic embryogenesis in larch (Larix leptolepis) - Jun-Hong Zhang; Shou-Gong Zhang; Shui-Gen Li; Su-Ying Han; Wan-Feng Li; Xin-Min Li; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

The post-transcriptional regulation of LaSCL6 by miR171 during maintenance of embryogenic potential in Larix kaempferi (Lamb.) Carr. - Wan-Feng Li; Shou-Gong Zhang; Su-Ying Han; Tao Wu; Jun-Hong Zhang; Li-Wang Qi (Tree Genetics & Genomes, 2014)

The up-regulation of cysteine-rich protein 61 induced by transforming growth factor beta enhances osteosarcoma cell migration - Jun Chen; Yang Song; Jing Yang; Li Gong; Peng Zhao; Yong Zhang; Haichuan Su (Molecular and Cellular Biochemistry, 2013)

Influence of serum adiponectin level and SNP +45 polymorphism of adiponectin gene on myocardial fibrosis - Cheng-jun Yan; Su-mei Li; Qiang Xiao; Yan Liu; Jian Hou; Ai-fang Chen; Li-ping Xia; Xiu-chang Li (Journal of Zhejiang University-SCIENCE B, 2013)

MicroRNA-200b targets CREB1 and suppresses cell growth in human malignant glioma - Biao Peng; Su Hu; Qinming Jun; Dongdong Luo; Xun Zhang; Hailin Zhao; Dan Li (Molecular and Cellular Biochemistry, 2013)

Acid loading stimulates rat glomerular mesangial cells proliferation through Na+–H+ exchanger isoform 1 (NHE1)-dependent pathway - Kun Li; Wei Su; Man Li; Chang-jie Chen; Yong-yu Li; Lin-yun Lai; Ming-min Zhang; Shao-jun Liu; Jakub Fichna; Ai Peng; Chuan-ming Hao; Yong Gu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Regulation of LaMYB33 by miR159 during maintenance of embryogenic potential and somatic embryo maturation in Larix kaempferi (Lamb.) Carr. - Wan-Feng Li; Shou-Gong Zhang; Su-Ying Han; Tao Wu; Jun-Hong Zhang; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Identification of two SCAR markers co-segregated with the dominant Ms and recessive ms alleles in onion (Allium cepa L.) - Yan Yan Yang; Yu Meng Huo; Jun Miao; Bing Jiang Liu; Su Ping Kong; Li Min Gao; Chang Liu; Zhen Bao Wang; Yasuki Tahara; Hidemi Kitano; Xiong Wu (Euphytica, 2013)

Environmental capacity of petroleum hydrocarbon pollutants in Jiaozhou Bay, China: Modeling and calculation - Keqiang Li; Ying Su; Jun Ying; Xiulin Wang; Jinbo Mu (Journal of Ocean University of China, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Episodic orogeny deduced from coeval sedimentary sequences in the foreland basin and its implication for uplift process of Longmen Mountain, China - Yong Li; De-chen Su; Rong-jun Zhou; Hai-bing Li; Alexander L. Densmore; Liang Yan; Zhao-kun Yan (Journal of Mountain Science, 2013)

The occurrence of gold in hydrothermal sulfide at Southwest Indian Ridge 49.6°E - Jun Ye; Xuefa Shi; Yaomin Yang; Naisheng Li; Jihua Liu; Wenchao Su (Acta Oceanologica Sinica, 2012)

Effects of indole-3-acetic acid and auxin transport inhibitors on the style curvature of three Alpinia species (Zingiberaceae) - Yin-Ling Luo; Ting-Ju Bi; Dong Li; Zhi-Long Su; Chuan Tao; Yan-Jiang Luo; Qing-Jun Li (Acta Physiologiae Plantarum, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Effects of SCR-3 on the immunosuppression accompanied with the systemic inflammatory response syndrome - Jun Li; Jie Niu; Shan Ou; Zhan-Yong Ye; Deng-Qun Liu; Feng-Chao Wang; Yong-Ping Su; Jun-Ping Wang (Molecular and Cellular Biochemistry, 2012)

Effects of a non-selective TRPC channel blocker, SKF-96365, on melittininduced spontaneous persistent nociception and inflammatory pain hypersensitivity - Jing Ding; Jia-Rui Zhang; Yan Wang; Chun-Li Li; Dan Lu; Su-Min Guan; Jun Chen (Neuroscience Bulletin, 2012)

Identification and expression of a putative LPS-induced TNF-α factor from Asiatic hard clam Meretrix meretrix - Hong-jun Li; Qing Yang; Xiang-gang Gao; Hao Su; Juan Wang; Chong-bo He (Molecular Biology Reports, 2012)

Association of type 2 diabetes susceptibility genes (TCF7L2, SLC30A8, PCSK1 and PCSK2) and proinsulin conversion in a Chinese population - Xiaoya Zheng; Wei Ren; Suhua Zhang; Jingjing Liu; Sufang Li; Jinchao Li; Ping Yang; Jun He; Shaochu Su; Ping Li (Molecular Biology Reports, 2012)

The effect of down regulation of calcineurin Aα by lentiviral vector-mediated RNAi on the biological behavior of small-cell lung cancer and its bone metastasis - Ning-Qiang Ma; Li-Li Liu; Jie Min; Jun-Wei Wang; Wei-Feng Jiang; Yan Liu; Yan-Guo Feng; Hai-Chuan Su; Ying-Ming Feng; He-Long Zhang (Clinical & Experimental Metastasis, 2011)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

Insulin-like growth factor-1 receptor activation prevents hydrogen peroxide-induced oxidative stress, mitochondrial dysfunction and apoptosis - Chang-Ning Hao; Yong-Jian Geng; Fan Li; Tong Yang; Ding-Feng Su; Jun-Li Duan; Yangxin Li (Apoptosis, 2011)

Differential Gene Expression Analysis of Yunnan Red Pear, Pyrus Pyrifolia, During Fruit Skin Coloration - Xiaodong Zhang; Andrew C Allan; Qiong Yi; Limei Chen; Kunzhi Li; Qun Shu; Jun Su (Plant Molecular Biology Reporter, 2011)

The complete mitochondrial genome of the hard clam Meretrix meretrix - Chong-bo He; Jian Wang; Xiang-gang Gao; Wen-tao Song; Hong-jun Li; Yun-feng Li; Wei-dong Liu; Hao Su (Molecular Biology Reports, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

A large outbreak of hand, foot, and mouth disease caused by EV71 and CAV16 in Guangdong, China, 2009 - Wu De; Ke Changwen; Li Wei; Corina Monagin; Yan Jin; Ma Cong; Zen Hanri; Su Jun (Archives of Virology, 2011)

A novel human derived cell-penetrating peptide in drug delivery - Jian Zhao; Peng Gao; Wei Xiao; Li-Qiang Fan; Fu-Jun Wang; Su-Xia Li; Jian-Wen Liu (Molecular Biology Reports, 2011)

Genetic polymorphism analysis of 15 STR loci in Chinese Hui ethnic group residing in Qinghai province of China - Ya-jun Deng; Bo-feng Zhu; Chun-mei Shen; Hong-dan Wang; Jing-feng Huang; Yuan-zhe Li; Hai-xia Qin; Hao-fang Mu; Jie Su; Jie Wu; Bo Zhang; Shuan-liang Fan (Molecular Biology Reports, 2011)

Characterization of Five Putative Acyl Carrier Protein (ACP) Isoforms from Developing Seeds of Arachis hypogaea L. - Meng-Jun Li; Xing-Jun Wang; Lei Su; Yu-Ping Bi; Shu-Bo Wan (Plant Molecular Biology Reporter, 2010)

Influence of 14-day hind limb unloading on isolated muscle spindle activity in rats - Xue Hong Zhao; Xiao Li Fan; Xin Ai Song; Su Di Wu; Jun Chan Ren; Ming Xia Chen (Journal of Muscle Research and Cell Motility, 2010)

SHRIMP U-Pb dating and Hf isotopic analyses of Middle Ordovician meta-cumulate gabbro in central Qiangtang, northern Tibetan Plateau - QingGuo Zhai; Jun Wang; Cai Li; Li Su (Science China Earth Sciences, 2010)

The interaction between interferon-induced protein with tetratricopeptide repeats-1 and eukaryotic elongation factor-1A - Hong-Tao Li; Yong-Ping Su; Tian-Min Cheng; Jian-Ming Xu; Jie Liao; Ji-Chuan Chen; Chang-You Ji; Guo-Ping Ai; Jun-Ping Wang (Molecular and Cellular Biochemistry, 2010)

Treatment strategies for Parkinson’s disease - Hong Yuan; Zhen-Wen Zhang; Li-Wu Liang; Quan Shen; Xiang-Dang Wang; Su-Mei Ren; Hong-Jie Ma; Shu-Jun Jiao; Ping Liu (Neuroscience Bulletin, 2010)

Protein sumoylation sites prediction based on two-stage feature selection - Lin Lu; Xiao-He Shi; Su-Jun Li; Zhi-Qun Xie; Yong-Li Feng; Wen-Cong Lu; Yi-Xue Li; Haipeng Li; Yu-Dong Cai (Molecular Diversity, 2010)

An improved process for cell disruption and astaxanthin extraction from Phaffia rhodozyma - An-Feng Xiao; Hui Ni; Hui-Nong Cai; Li-Jun Li; Wen-Jin Su; Qiu-Ming Yang (World Journal of Microbiology and Biotechnology, 2009)

Des-γ-carboxy prothrombin stimulates human vascular endothelial cell growth and migration - Su-Bo Wang; Yan-Na Cheng; Shu-Xiang Cui; Julia Li Zhong; S. G. Ward; Li-Rui Sun; Ming-Hui Chen; Norihiro Kokudo; Wei Tang; Xian-Jun Qu (Clinical & Experimental Metastasis, 2009)

Overexpression of Thellungiella halophila H+-PPase (TsVP) in cotton enhances drought stress resistance of plants - Su-Lian Lv; Li-Jun Lian; Pei-Lin Tao; Zhao-Xia Li; Ke-Wei Zhang; Ju-Ren Zhang (Planta, 2009)

Notch signaling regulates the FOXP3 promoter through RBP-J- and Hes1-dependent mechanisms - Hai-Feng Ou-Yang; Hong-Wei Zhang; Chang-Gui Wu; Ping Zhang; Jian Zhang; Jun-Chang Li; Li-Hong Hou; Fei He; Xin-Yu Ti; Li-Qiang Song; Su-Zhen Zhang; Lei Feng; et al. (Molecular and Cellular Biochemistry, 2009)

Isolation and characterization of microsatellite markers for the endangered Taxus yunnanensis - Ying-Chun Miao; Jian-Rong Su; Zhi-Jun Zhang; Hui Li; Jing Luo; Ya-Ping Zhang (Conservation Genetics, 2008)

Characterization of seven genomic and one dbEST-derived microsatellite loci in the river mangrove Aegiceras corniculatum (Myrsinaceae) - Guo-Qing Chen; Lin-Feng Li; Gang Hao; Su-Hua Shi; Xue-Jun Ge (Conservation Genetics, 2008)

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells - Xue-Ping Zhang; Gang Zheng; Lian Zou; Hui-Ling Liu; Li-Hong Hou; Peng Zhou; Dan-Dan Yin; Qi-Jun Zheng; Liang Liang; Su-Zhen Zhang; Lei Feng; Li-Bo Yao; et al. (Molecular and Cellular Biochemistry, 2007)

A Pilot Study of Transcription Unit Analysis in Rice Using Oligonucleotide Tiling-path Microarray - Viktor Stolc; Lei Li; Xiangfeng Wang; Xueyong Li; Ning Su; Waraporn Tongprasit; Bin Han; Yongbiao Xue; Jiayang Li; Michael Snyder; Mark Gerstein; Jun Wang; et al. (Plant Molecular Biology, 2005)

Modeling water and carbon fluxes above summer maize field in North China Plain with back-propagation neural networks - Zhong Qin; Gao-li Su; Qiang Yu; Bing-min Hu; Jun Li (Journal of Zhejiang University-SCIENCE B, 2005)

Study of setting up the forest Resources Management Information System based on WEBGIS - Su-li Wu; Quan-sheng Lou; Zhi-jie Quan; Xiao-jun Li (Chinese Geographical Science, 2003)